FLEXIBLE POROUS DISSOLVEABLE SOLID SHEET ARTICLE CONTAINING A CATIONIC SURFACTANT - Patent application
By adding an appropriate amount of plasticizer to the pre-wet slurry of the sheet, adjusting its weight ratio to the cationic surfactant, and through appropriate drying process, the problem of instability in the pre-bubble slurry leading to low open cell content in the sheet is solved, and the sheet with high open cell content and uniform pore structure is achieved, which significantly improves its dissolution performance and simplicity of the production process.
Patent Information
- Application Number
- JP2022536564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-02-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-02-20
AI Technical Summary
When forming a breathable solid sheet containing a cationic surfactant, the instability of the pre-bubble slurry results in the amount of open cell content of the sheet being lower than expected, making it difficult to achieve in industrial scale production.
By adding an appropriate amount of plasticizer to the pre-wet slurry of the sheet, adjusting its weight ratio to the cationic surfactant is between 0.9 and 2, a more stable pre-bubble slurry is formed, and a sheet with high open cell content and uniform pore structure is formed by a proper drying process.
The pore structure stability and pore uniformity of the sheet are improved, the dissolution performance in water is significantly improved, and the process flow of industrial-scale production is simplified.
Smart Images

Figure 0007648629000021 
Figure 0007648629000022 
Figure 0007648629000023
Abstract
Description
[Technical field]
[0001] The present invention relates to a flexible porous dissolvable solid sheet article containing a cationic surfactant. [Background technology]
[0002] Flexible dissolvable solid sheets containing surfactants and / or other active ingredients in a water-soluble polymer carrier or matrix are well known. The water-soluble polymer can function as a film former, structurant, and carrier for other ingredients in the solid sheet. Such sheets can be used as fabric care products, home care products, hair care products, beauty care products, personal care products, and the like. In particular, such flexible dissolvable sheets may contain cationic surfactants as fabric care actives (e.g., fabric conditioners), home care actives (e.g., dishwashing agents), hair care actives (e.g., hair conditioners), beauty care actives, and / or personal care actives, and when dissolved in water, can be particularly useful for delivering such actives. Compared to conventional liquid-form fabric care, home care, hair care, beauty care, and / or personal care products in the same product category, such sheets have better structural integrity, are more concentrated, and are easier to store, transport / ship, carry, and handle. Compared to solid tablet forms within the same product category, such sheets are more flexible, less brittle and have better sensory appeal to consumers.
[0003] To improve solubility, WO 2010 / 077627 discloses a batch process for forming a porous sheet having an open-celled foam (OCF) structure characterized by an open cell content percentage of about 80% to 100%. Specifically, a premix of raw materials including a water-soluble polymer carrier is first formed, which is vigorously aerated to introduce air bubbles into the premix, and then thermally dried in batch (e.g., in a convection oven or microwave oven) to form a porous sheet having the desired OCF structure. However, the inventors of the present invention have discovered that in the process of forming a porous solid sheet containing a cationic surfactant, the aerated premix may be less stable than desired. In other words, the air bubbles formed in the aerated premix may collapse a short time after aeration. In this case, the formed porous sheet may have a lower open cell content percentage than expected, or it may be necessary to thermally dry the aerated premix as soon as possible or immediately after aeration to ensure the formation of the desired OCF structure. This can create undesirable difficulties in designing a manufacturing process for such porous sheets, especially in large scale production, since it may not be practical to dry the aerated premix immediately after aeration in industrial production. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2010 / 077627 Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, there is a need to improve the stability of the aerated premix in the process of forming a porous sheet containing a cationic surfactant in order to obtain a porous sheet with further improved porosity and / or to facilitate industrial production. [Means for solving the problem]
[0006] The present invention provides a flexible porous dissolvable solid sheet article comprising a water-soluble polymer, a plasticizer, and a cationic surfactant, the weight ratio of the plasticizer to the cationic surfactant being about 0.9 to about 2. The present invention further provides a process for preparing the solid sheet article, the process comprising: a) preparing a wet premix comprising a water-soluble polymer, a plasticizer, and a cationic surfactant, the weight ratio of the plasticizer to the cationic surfactant being about 0.9 to about 2; b) aerating the wet premix to form an aerated wet premix; c) forming the aerated wet premix into a sheet; and d) drying the formed sheet. In particular, the weight ratio of the plasticizer to the cationic surfactant may be about 1 to about 1.8, preferably about 1.1 to about 1.7, more preferably about 1.2 to about 1.6.
[0007] Surprisingly, the present inventors have unexpectedly discovered that the stability of the aerated premix can be significantly improved when the ratio of plasticizer to cationic surfactant in the premix is within a preferred range, for example, from about 0.9 to about 2. The improved stability can further result in significantly improved pore structure, thereby resulting in significantly improved dissolution profiles that are desirable to consumers. The improved stability can also result in significantly improved flexibility in the manufacturing process of solid sheet articles.
[0008] In one aspect, the invention relates to a flexible porous dissolvable solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant, the solid sheet article being characterized by (i) a percent open cell content of from about 80% to about 100%, and (ii) an overall average pore size of from about 100 μm to about 2000 μm, and the weight ratio of plasticizer to cationic surfactant can be from about 0.9 to about 2.
[0009] The solid sheet article may preferably comprise from about 1% to about 65%, preferably from about 10% to about 60%, more preferably from about 15% to about 55%, even more preferably from 20% to 50%, and most preferably from 22% to 40% of the total weight of the solid sheet article. In a preferred but not required embodiment of the invention, the plasticizer may be glycerin.
[0010] The solid sheet article may preferably comprise about 1% to about 50%, preferably about 5% to about 45%, more preferably about 10% to about 40%, and most preferably about 15% to about 35% of the total weight of the solid sheet article. In a preferred but not required embodiment of the present invention, the cationic surfactant may be selected from the group consisting of N,N-di(acyloxyethyl)-N,N-dimethylammonium chloride, N,N-di(acyloxyisopropyl)-N,N-dimethylammonium methyl sulfate, N,N-di(acyloxyethyl)-N,N-methylhydroxyethylammonium methyl sulfate, C12-C22 alkyl trimethylammonium bromide, C12-C22 alkyl trimethylammonium chloride, such as coconut trimethylammonium chloride and lauryl trimethylammonium chloride, and any combination thereof. Preferably, the acyl group is derived from animal fat, unsaturated fatty acid, and polyunsaturated fatty acid.
[0011] The solid sheet article may preferably comprise from about 1% to about 60%, preferably from about 5% to about 50%, more preferably from about 10% to about 45%, and most preferably from about 15% to about 40% of the total weight of the solid sheet article of a water soluble polymer. In a preferred but not required embodiment of the invention, the water soluble polymer may be selected from the group consisting of polyvinyl alcohol, starch, and any combination thereof.
[0012] Additionally, in preferred but not required embodiments of the present invention, the solid sheet article may comprise from 0.01% to about 20%, preferably from 0.1% to about 12%, more preferably from 0.5% to about 8%, and most preferably from 1% to 5% of a nonionic surfactant by total weight of the solid sheet article.
[0013] The flexible porous dissolvable solid sheet article of the present invention comprises: an open cell content of 85% to 100%, preferably 90% to 100%, and / or an overall average pore size of 150 μm to 1000 μm, preferably 200 μm to 600 μm, and / or an average cell wall thickness of 5 μm to 200 μm, preferably 10 μm to 100 μm, more preferably 10 μm to 80 μm, and / or a final moisture content of 0.5% to 25% by weight of the solid sheet article, preferably 1% to 20% by weight, more preferably 3% to 15% by weight, and / or a thickness of each sheet between 0.5 mm and 4 mm, preferably between 0.7 mm and 3 mm, more preferably between 0.8 mm and 2 mm, and most preferably between 1 mm and 1.5 mm; and / or 50g / m 2 ~250g / m 2 , preferably 80 g / m 2 ~230g / m 2 , more preferably 100 g / m 2 ~220g / m 2 and / or 0.05g / cm 3 ~0.5g / cm 3 , preferably 0.06 g / cm 3 ~0.4g / cm 3 , more preferably 0.07 g / cm 3 ~0.3g / cm 3 , most preferably 0.08 g / cm 3 ~0.25g / cm 3 and / or 0.03m 2 / g~0.25m 2 / g, preferably 0.04m 2 / g~0.22m 2 / g, more preferably 0.05m 2 / g~0.2m 2 / g, most preferably 0.1m 2 / g~0.18m 2It can be further characterized by a specific surface area in g / g.
[0014] Additionally, the solid sheet article of the present invention may comprise two or more flexible porous dissolvable sheets, with the coating composition being present on at least one surface of at least one of the two or more sheets, provided that the coating composition is not present on any exterior surface of the solid sheet article.
[0015] In another aspect, the present invention relates to a process for making a sheet article, the process comprising: a) mixing a water-soluble polymer, a plasticizer, and a cationic surfactant at 40° C. and 1 s -1 The method includes the steps of: preparing a wet premix having a viscosity of about 1,000 cp to about 25,000 cp as measured by a 100% sieve pressure, the weight ratio of plasticizer to cationic surfactant being about 0.9 to about 2; a) aerating the wet premix to form an aerated wet premix having a density of about 0.05 to about 0.7 g / mL, preferably about 0.15 g / mL to about 0.6 g / mL, more preferably about 0.2 g / mL to about 0.5 g / mL, and most preferably about 0.25 g / mL to about 0.45 g / mL; c) forming the aerated wet premix into a sheet having opposing first and second surfaces; and d) drying the formed sheet to produce a sheet article. Preferably, step d) may be carried out for a period of about 5 minutes to about 300 minutes, preferably about 10 minutes to about 120 minutes. Preferably, the drying in step d) may be carried out at a temperature of about 70°C to about 200°C, preferably about 90°C to about 140°C, along a heating direction forming a decreasing temperature gradient from the first side to the second side of the formed sheet, the heating direction being substantially opposite to the direction of gravity for more than half the drying time, preferably for more than 75% of the drying time.
[0016] These and other aspects of the invention will become more apparent from a reading of the following detailed description. [Brief description of the drawings]
[0017] [Figure 1] 1 shows a convection heating / drying configuration for making flexible porous dissolvable solid sheet articles in a batch process. [Diagram 2] 1 shows a microwave heating / drying configuration for making flexible porous dissolvable solid sheet articles in a batch process. [Diagram 3] 1 shows an impingement oven heating / drying configuration for making flexible porous dissolvable solid sheet articles in a continuous process. [Figure 4] 1 shows a bottom conduction heating / drying configuration for making flexible porous dissolvable sheets in a batch process. [Diagram 5] 1 shows a rotating drum heating / drying configuration for making another flexible porous dissolvable sheet in a continuous process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] I. Definition As used herein, the term "flexible" refers to the ability of an article to withstand stress when bent 90° along a centerline perpendicular to its length without breaking or significant disruption. Preferably, such articles are capable of undergoing significant elastic deformation and are characterized by a Young's modulus of 5 GPa or less, preferably 1 GPa or less, more preferably 0.5 GPa or less, and most preferably 0.2 GPa or less.
[0019] As used herein, the term "solubility" refers to the ability of an article to completely or substantially dissolve in a sufficient amount of deionized water at 20° C. and atmospheric pressure within 8 hours without any agitation, with less than 5% by weight remaining as an insoluble residue.
[0020] As used herein, the term "solid" refers to the ability of an article to substantially retain its shape (i.e., without any visible change in its shape) at 20° C. and atmospheric pressure when the article is unconstrained and no external forces are applied to the article.
[0021] As used herein, the term "sheet" refers to a non-fibrous structure having a three-dimensional shape, i.e., thickness, length, and width, while the aspect ratios of length to thickness and width to thickness are both at least about 5:1, and the length to width ratio is at least about 1:1. Preferably, the aspect ratios of length to thickness and width to thickness are both at least about 10:1, more preferably at least about 15:1, and most preferably at least about 20:1, and the aspect ratio of length to width is preferably at least about 1.2:1, more preferably at least about 1.5:1, and most preferably at least about 1.618:1.
[0022] As used herein, the term "bottom surface" refers to the surface of the flexible porous dissolvable solid sheet article of the present invention that is in direct contact with the support surface on which the sheet of aerated wet premix is placed during the drying process, while the term "top surface" refers to the surface of the sheet article opposite the bottom surface. Furthermore, such a solid sheet article can be divided along its thickness into three regions, including a top region adjacent its top surface, a bottom region adjacent its bottom surface, and a middle region located between the top and bottom regions. The top, middle, and bottom regions are equal in thickness, i.e., each has a thickness of about 1 / 3 of the total thickness of the sheet article.
[0023] As used herein, the term "open cell foam" or "open cell pore structure" refers to a solid interconnected polymer-containing matrix that contains a gas, typically a gas (such as air), and defines a network of voids or cells that do not collapse the foamed structure during the drying process, thereby maintaining physical strength and solid coherence. The interconnectedness of the structure may be described by the percent open cell content, as measured by Test 3 disclosed below.
[0024] As used herein, the term "water solubility" refers to the ability of a sample material to completely dissolve or disperse in water without leaving any visible solids or forming any visible separate phases, when at least about 25 grams, preferably at least about 50 grams, more preferably at least about 100 grams, and most preferably at least about 200 grams of such material are placed in one liter (1 L) of deionized water at 20° C. and atmospheric pressure with sufficient agitation.
[0025] As used herein, the terms "aerate", "aerating" or "aeration" refer to the process of introducing gas into a liquid or pasty composition by mechanical and / or chemical means.
[0026] As used herein, the term "heating direction" refers to a direction in which a heat source applies thermal energy to an article, resulting in a temperature gradient in such an article that decreases from one side of such an article to the other side. For example, if a heat source located on one side of an article applies thermal energy to the article to generate a temperature gradient that decreases from one side to the other side, the heating direction is then considered to extend from one side to the other side. If both sides of such an article or different portions of such an article are heated simultaneously without an observable temperature gradient across such an article, then the heating occurs in a non-directional manner and there is no heating direction.
[0027] As used herein, the terms "substantially opposite" or "substantially offset" refer to two directions or two lines that have an offset angle between them of 90° or more.
[0028] As used herein, the terms "substantially aligned" or "substantial alignment" refer to two directions or two lines that have an offset angle between them of less than 90°.
[0029] As used herein, the term "primary heat source" refers to a heat source that provides more than 50%, preferably more than 60%, more preferably more than 70%, and most preferably more than 80% of the total heat energy absorbed by an object (e.g., a sheet of aerated wet premix according to the present invention).
[0030] As used herein, the term "controlled surface temperature" refers to a surface temperature that is relatively stable, i.e., having less than + / - 20% variation, preferably less than + / - 10% variation, and more preferably less than + / - 5% variation.
[0031] The terms "essentially free of" or "essentially free from" mean that the indicated substance is present in such small amounts that it has not been intentionally added to a composition or product, or preferably is not present in such composition or product at concentrations detectable by analysis. Compositions or products may be included in which the indicated substance is present only as an impurity of one or more substances intentionally added to such composition or product.
[0032] II. Formulations of the Solid Sheet Articles of the Present Invention The solid sheet article of the present invention comprises a water soluble polymer, a plasticizer, and a cationic surfactant. Additionally, the solid sheet article of the present invention may further comprise one or more additional ingredients.
[0033] In some embodiments, the solid sheet article of the present invention may include two or more overlapping flexible porous dissolvable sheets. In this case, the coating composition may be present on at least one surface of at least one of the two or more sheets, provided that the coating composition is not present on any outer surface of the solid sheet article. In other words, the coating composition may be added between the sheets of the solid sheet article.
[0034] 1. Water-soluble polymers As mentioned above, the flexible porous dissolvable solid sheet articles of the present invention may be formed by a wet premix comprising a water-soluble polymer, a plasticizer, and a cationic surfactant. Such water-soluble polymers may function as film formers, structuring agents, and other active ingredients (e.g., surfactants, emulsifiers, builders, chelating agents, fragrances, colorants, etc.) in the resulting solid sheet article.
[0035] Preferably, the wet premix may comprise from about 1% to about 30% water soluble polymer by weight of the premix, and in one embodiment from about 5% to about 20% water soluble polymer by weight of the premix, and in one embodiment from about 7% to about 15% water soluble polymer by weight of the premix.
[0036] After drying, the water soluble polymer is preferably present in the flexible porous dissolvable solid sheet article of the invention in an amount ranging from about 1% to about 60%, preferably from about 5% to about 50%, more preferably from about 10% to about 45%, even more preferably from about 15% to about 40%, and most preferably from about 20% to about 30% of the total weight of the solid sheet article. In particularly preferred embodiments of the invention, the total amount of water soluble polymer present in the flexible porous dissolvable solid sheet article of the invention is no more than about 25% of the total weight of such article.
[0037] Suitable water-soluble polymers for the practice of the present invention may be selected having a weight average molecular weight ranging from about 5,000 to about 400,000 Daltons, more preferably from about 10,000 to about 300,000 Daltons, even more preferably from about 15,000 to about 200,000 Daltons, and most preferably from about 20,000 to about 150,000 Daltons. The weight average molecular weight is calculated by adding the average molecular weight of each polymer raw material and multiplying by their relative weight percentage by weight of the total weight of polymer present in the porous solid. The weight average molecular weight of the water-soluble polymer used herein may affect the viscosity of the wet premix, which in turn may affect the number and size of bubbles during the aeration step, and the pore expansion / opening results during the drying step. Additionally, the weight average molecular weight of the water-soluble polymer may affect the overall film-forming properties of the wet premix, and its compatibility / incompatibility with certain surfactants.
[0038] Water soluble polymers of the present invention may include, but are not limited to, synthetic polymers including polyvinyl alcohol, polyvinylpyrrolidone, polyalkylene oxides, polyacrylates, caprolactams, polymethacrylates, polymethylmethacrylates, polyacrylamides, polymethylacrylamides, polydimethylacrylamides, polyethylene glycol monomethacrylates, copolymers of acrylic acid and methyl acrylate, polyurethanes, polycarboxylic acids, polyvinyl acetates, polyesters, polyamides, polyamines, polyethyleneimines, maleic acid / (acrylate or methacrylate) copolymers, copolymers of methyl vinyl ether and maleic anhydride, copolymers of vinyl acetate and crotonic acid, copolymers of vinylpyrrolidone and vinyl acetate, copolymers of vinylpyrrolidone and caprolactam, copolymers of vinylpyrrolidone / vinyl acetate, copolymers of anionic, cationic and amphoteric monomers, and combinations thereof.
[0039] The water soluble polymers of the present invention may also be selected from polymers of natural origin including those of vegetable origin with examples such as karaya gum, tragacanth gum, gum arabic, acemannan, konjac mannan, acacia gum, ghatti gum, whey protein isolate, and soy protein isolate, seed extracts including guar gum, locust bean gum, quince seed, and psyllium seed, seaweed extracts such as carrageenan, alginic acid, and agar, fruit extracts (pectins); those of microbial origin including xanthan gum, gellan gum, pullulan, hyaluronic acid, chondroitin sulfate, and dextran; and those of animal origin including casein, gelatin, keratin, keratin hydrolysate, keratin sulfonate, albumin, collagen, glutelin, glucagon, gluten, zein, and shellac.
[0040] Modified natural polymers may also be used as water-soluble polymers in the present invention.Suitable modified natural polymers include, but are not limited to, cellulose derivatives such as hydroxypropylmethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, methylcellulose, hydroxypropylcellulose, ethylcellulose, carboxymethylcellulose, cellulose acetate phthalate, nitrocellulose and other cellulose ethers / esters, and guar derivatives such as hydroxypropyl.
[0041] The water-soluble polymer of the present invention may comprise starch. As used herein, the term "starch" includes both naturally occurring starch and modified starch. Typical natural sources of starch can include cereals, tubers, roots, legumes and fruits. More specific natural sources can include corn, beans, potatoes, bananas, barley, wheat, rice, sago, amaranth, tapioca, arrowroot, canna, sorghum, and their waxy or higher amylase species. Native starch can be modified by any modification method known in the art to form modified starches, including physically modified starches such as sheared or thermally inhibited starches, crosslinked, acetylated, and organic esterified, hydroxyethylated, and hydroxypropylated, phosphorylation, and inorganic esterified, chemically modified starches such as cationic, anionic, nonionic, amphoteric, and zwitterionic, and their succinate and substituted succinate derivatives, conversion products derived from starch including oxidation, enzymatic conversion, acid hydrolysis, heat or acid dextrinization, fluid or thin boiled starches prepared by heat and / or sheared products, heat and / or sheared products that may be useful herein, and pregelatinized starches known in the art.
[0042] Preferred water-soluble polymers of the present invention include polyvinyl alcohol, polyvinylpyrrolide, polyalkylene oxide, starch and starch derivatives, pullulan, gelatin, hydroxypropylmethylcellulose, methylcellulose, and carboxymethylcellulose. More preferred water-soluble polymers of the present invention are selected from the group consisting of polyvinyl alcohol, starch, and any combination thereof.
[0043] The polyvinyl alcohol may be characterized by a degree of hydrolysis ranging from about 40% to about 100%, preferably from about 50% to about 95%, more preferably from about 65% to about 92%, and most preferably from about 70% to about 90%. Commercially available polyvinyl alcohols include those available under the tradename CELVOL from Celanese Corporation (Texas, USA), including but not limited to CELVOL 523, CELVOL 530, CELVOL 540, CELVOL 518, CELVOL 513, CELVOL 508, CELVOL 504, those available under the tradenames Mowiol® and POVAL® from Kuraray Europe GmbH (Frankfurt, Germany), and PVA 1788 (also referred to as PVA BP17), available from a variety of sources including Lubon Vinylon Co. (Nanjing, China), and combinations thereof.
[0044] In a particularly preferred embodiment of the present invention, the flexible porous dissolvable solid sheet article comprises from about 1% to about 60%, preferably from about 5% to about 50%, more preferably from about 10% to about 40%, even more preferably from about 15% to about 40%, and most preferably from about 20% to about 35% of the total weight of such article of polyvinyl alcohol having a weight average molecular weight in the range of from about 80,000 to about 150,000 Daltons and a degree of hydrolysis in the range of from about 80% to about 90%.
[0045] In another particularly preferred embodiment of the present invention, the flexible porous dissolvable solid sheet article comprises about 1% to about 60%, preferably about 5% to about 50%, more preferably about 10% to about 40%, even more preferably about 15% to about 35%, and most preferably about 20% to about 30% of the total weight of such article of polyvinyl alcohol having a weight average molecular weight in the range of about 80,000 to about 150,000 Daltons and a degree of hydrolysis in the range of about 80% to about 90%, in addition to about 0.001% to about 5%, preferably about 0.01% to about 4.5%, more preferably about 0.1% to about 4%, even more preferably about 1% to about 4%, and most preferably about 2% to about 4% of the total weight of such article of starch. The presence of starch can help reduce the overall concentration of water-soluble polymer required and / or provide other advantages in terms of the physical / chemical properties described herein. However, without wishing to be bound by any theory, it is believed that too much starch may impair the solubility, structural integrity, and / or elasticity of the sheet article. Thus, in preferred embodiments of the present invention, the solid sheet article desirably comprises no more than about 5% starch, preferably from about 0% to about 4.5%, and more preferably from about 0% to about 4%, by weight of the solid sheet article.
[0046] In another particularly preferred embodiment of the present invention, a flexible porous dissolvable solid sheet article comprises from about 1% to about 60%, preferably from about 2% to about 30%, more preferably from about 3% to about 20%, even more preferably from about 4% to about 15%, and most preferably from about 4% to about 10% of the total weight of such article of a first polyvinyl alcohol having a weight average molecular weight in the range of about 20,000 to about 30,000 Daltons and a degree of hydrolysis in the range of about 80% to about 90%, in addition to from about 2% to about 60%, preferably from about 4% to about 40%, more preferably from about 6% to about 30%, even more preferably from about 8% to about 25%, and most preferably from about 12% to about 22% of the total weight of such article of a second polyvinyl alcohol having a weight average molecular weight in the range of about 50,000 to about 150,000 Daltons and a degree of hydrolysis in the range of about 80% to about 90%.
[0047] 2. Plasticizers The flexible porous dissolvable solid sheet article of the present invention preferably comprises a plasticizer in an amount ranging from about 1% to about 65%, preferably from about 10% to about 60%, more preferably from about 15% to about 55%, even more preferably from about 20% to about 50%, and most preferably from about 22% to about 40% of the total weight of the solid sheet article. Correspondingly, the wet premix used to form such a solid sheet article may comprise from about 0.1% to about 50%, preferably from about 1% to about 40%, more preferably from about 5% to about 30%, even more preferably from about 8% to about 25%, and most preferably from about 10% to about 20% by weight of the wet premix of plasticizer.
[0048] Plasticizers suitable for use in the present invention include, for example, polyols, copolyols, polycarboxylic acids, polyesters, dimethicone copolyols, and the like.
[0049] Examples of useful polyols include, but are not limited to, glycerin, diglycerin, ethylene glycol, polyethylene glycol (especially 200-600), propylene glycol, butylene glycol, pentylene glycol, glycerol derivatives (such as propoxylated glycerol), glycidol, cyclohexanedimethanol, hexanediol, 2,2,4-trimethylpentane-1,3-diol, pentaerythritol, urea, sugar alcohols (such as sorbitol, mannitol, lactitol, xylitol, maltitol, and other mono- and polyhydric alcohols), mono-, di-, and oligo-saccharides (such as fructose, glucose, sucrose, maltose, lactose, high fructose corn syrup solids, and dextrins), ascorbic acid, sorbates, ethylene bisformamide, amino acids, and the like.
[0050] Examples of polycarboxylic acids include, but are not limited to, citric acid, maleic acid, succinic acid, polyacrylic acid, and polymaleic acid.
[0051] Examples of suitable polyesters include, but are not limited to, glycerol triacetate, acetylated monoglyceride, diethyl phthalate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, acetyl tributyl citrate.
[0052] Examples of suitable dimethicone copolyols include, but are not limited to, PEG-12 dimethicone, PEG / PPG-18 / 18 dimethicone, and PPG-12 dimethicone.
[0053] Other suitable plasticizers include alkyl and aryl phthalates; naphthalates; lactates (e.g., sodium, ammonium, and potassium salts); Sorbeth-30; urea; lactic acid; sodium pyrrolidone carboxylate (PCA); sodium hyaluronate or hyaluronic acid; soluble collagen; denatured proteins; monosodium L-glutamate; alpha and beta hydroxyl acids, such as glycolic acid, lactic acid, citric acid, maleic acid, and salicylic acid; glyceryl polymethacrylate; polymeric plasticizers, such as polyquaterniums; proteins and amino acids, such as glutamic acid, aspartic acid, and lysine; hydrogenated starch hydrolysates; other low molecular weight esters (e.g., C 2 ~C 10 esters of alcohols and acids; any other water soluble plasticizers known to those of ordinary skill in the food and plastics industries; and mixtures thereof.
[0054] Particularly preferred examples of plasticizers include glycerin, ethylene glycol, polyethylene glycol, propylene glycol, and mixtures thereof. The most preferred plasticizer is glycerin. The presence of a preferred plasticizer, such as glycerin, in the solid sheet may further provide an anti-wrinkle effect. In particular, when the solid sheet article contains a preferred amount of glycerin (e.g., 22% to 40% of the total weight of the solid sheet), the anti-wrinkle effect may be more pronounced.
[0055] 3. Cationic surfactants The solid sheet article of the article of the present invention comprises one or more cationic surfactants. The cationic surfactants may function as fabric care actives, such as fabric conditioners and / or fabric softeners, home care actives, hair care actives, beauty care actives, and / or personal care actives. In particular, the solid sheet article may comprise from about 1% to about 50%, preferably from about 5% to about 45%, more preferably from about 10% to about 40%, and most preferably from about 15% to about 35%, such as about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, or any range therebetween, of the total weight of the solid sheet article. Correspondingly, the wet premix used to form such solid sheet articles may comprise from about 0.1% to about 40% by weight of the wet premix, preferably from about 1% to about 35% by weight, more preferably from about 5% to about 30% by weight, even more preferably from about 8% to about 35% by weight, and most preferably from about 10% to about 30% by weight, such as about 10% by weight, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight, about 35% by weight, about 40% by weight, or any range therebetween, of cationic surfactant.
[0056] Specifically, the cationic surfactant may be a quaternary ammonium compound and / or an amine compound. More specifically, the cationic surfactant may be selected from the group consisting of diester quaternary ammonium (DEQA) compounds, mono-long alkyl quaternary ammonium compounds, di-long alkyl quaternary ammonium compounds, mono-long alkyl amine compounds, and any combination thereof. Even more specifically, the cationic surfactant may be selected from the group consisting of alkyl trimethyl ammonium compounds or their amine precursors, dialkyl dimethyl ammonium compounds or their amine precursors, methyl diethanol amine-based (MDEA-based) quaternary ammonium compounds or their amine precursors, methyl diisopropanol amine-based (MDIPA-based) quaternary ammonium compounds or their amine precursors, triethanol amine-based (TEA-based) quaternary ammonium compounds or their amine precursors, and any combination thereof. Most specifically, the cationic surfactant may be selected from the group consisting of behenyl trimethyl ammonium chloride; stearyl trimethyl ammonium chloride; cetyl trimethyl ammonium chloride; lauryl trimethyl ammonium chloride; hydrogenated tallow alkyl trimethyl ammonium chloride, dimethyl hydroxyethyl lauryl ammonium chloride, dialkyl (14-18) dimethyl ammonium chloride, ditallow alkyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dicetyl dimethyl ammonium chloride, N,N-di(acyloxyethyl)-N,N-dimethyl ammonium chloride, N,N-di(acyloxyisopropyl)-N,N-dimethyl ammonium methyl sulfate, N,N-di(acyloxyethyl)-N,N-methyl hydroxyethyl ammonium methyl sulfate, and any combination thereof. Exemplary cationic surfactants include diethyl ester dimethyl ammonium chloride (DEEDMAC), dipalmethyl hydroxyethyl ammonium methosulfate, coconut trimethyl ammonium chloride, and lauryl trimethyl ammonium chloride.
[0057] Further, in one embodiment, the cationic surfactant may be formed from the reaction product of a fatty acid with an amino alcohol, which results in a mixture of monoester, diester, and in one embodiment, triester compounds. In another embodiment, the cationic surfactant comprises one or more softener quaternary ammonium compounds, such as, but not limited to, monoalkyl quaternary ammonium compounds, dialkyl quaternary ammonium compounds, diamide quaternary compounds, diester quaternary ammonium compounds, monoester quaternary ammonium compounds, or combinations thereof.
[0058] Representative quaternary ammonium compounds include, but are not limited to, alkylated quaternary ammonium compounds, cyclic or cyclic quaternary ammonium compounds, aromatic quaternary ammonium compounds, diquaternary ammonium compounds, alkoxylated quaternary ammonium compounds, amidoamine quaternary ammonium compounds, ester quaternary ammonium compounds, and mixtures thereof. Examples of such compounds are described in U.S. Patent No. 7,381,697, column 3, line 43 to column 4, line 67, and U.S. Patent No. 7,135,451, column 5, line 1 to column 11, line 40. Also see U.S. Patent Nos. 4,424,134, 4,767,547, 5,545,340, 5,545,350, 5,562,849, and 5,574,179.
[0059] Preferably, the cationic surfactant may comprise a compound of the following formula: {R 4-m -N + -[ZYR 1 ] m}X - where each R is hydrogen, short chain C 1 ~C 6 , in one embodiment C 1 ~C 3 Alkyl or hydroxyalkyl groups (e.g., methyl, ethyl, propyl, hydroxyethyl, etc.), poly(C 2~3alkoxy), polyethoxy, benzyl, or mixtures thereof, each Z is independently selected from the group consisting of (CH 2 each Y may comprise -O-(O)C-, -C(O)-O-, -NR-C(O)-, or -C(O)-NR-, each m is 2 or 3, each n is 1 to about 4, in one embodiment 2, each R 1 The sum of the carbons in (plus 1 when Y is -O-(O)C- or -NR-C(O)-) is C 12 ~C 22 Or C 14 ~C 20 Each R 1 may be a hydrocarbyl or substituted hydrocarbyl group; X - may include any compatible anion. In one aspect, the compatible anion may include chloride, bromide, methyl sulfate, ethyl sulfate, sulfate, and nitrate. In another aspect, the compatible anion may include chloride or methyl sulfate. As used herein, when a diester is specified, it may include monoesters present.
[0060] In particular, a suitable cationic surfactant may be the reaction product of a fatty acid with a dialkylene triamine, for example in a molar ratio of about 2:1, which reaction product contains a compound of the formula: R 1 -C(O)-NH-R 2 -NH-R 3 -NH-C(O)-R 1 In the formula, R 1 , R 2 is as defined above, and each R 3 is C 1~6An example of these active ingredients is the reaction product of tallow acid, canola acid, or oleic acid with diethylenetriamine in a molecular ratio of about 2:1, the reaction product mixture containing N,N''-ditallowoyldiethylenetriamine, N,N''-dicanola-oyldiethylenetriamine, or N,N''-dioleoyldiethylenetriamine, respectively, of the formula: R 1 -C(O)-NH-CH 2 CH 2 -NH-CH 2 CH 2 -NH-C(O)-R 1 In the formula, R 2 and R 3 is a divalent ethylene group, and R 1 is as defined above, and R 1 Wherein is the oleoyl group of commercially available oleic acid derived from vegetable or animal sources, acceptable examples of this structure include EMERSOL® 223LL or EMERSOL® 7021 available from Henkel Corporation.
[0061] Another suitable cationic surfactant may have the formula: [R 1 -C(O)-NR-R 2 -N(R) 2 -R 3 -NR-C(O)-R 1 ] + X - In the formula, R, R 1 , R 2 , R 3 and X - is defined above. An example of this active ingredient is a difatty amidoamine based softener having the formula: [R 1 -C(O)-NH-CH 2 CH 2 -N(CH 3 )(CH 2 CH 2 OH)-CH 2 CH2 -NH-C(O)-R 1 ] + CH 3 SO 4 - In the formula, R 1 -C(O) is an oleoyl group, a soft tallow group, or a hydrogenated tallow group, available from Degussa under the trade names VARISOFT® 222LT, VARISOFT® 222, and VARISOFT® 110, respectively.
[0062] Another suitable cationic surfactant may have the general formula: [R 3 N + CH 2 CH(YR 1 )(CH 2 YR 1 )]X - In the formula, each Y, R, R 1 , and X - has the same meaning as above. An example of a preferred cationic surfactant is the "propyl" ester quaternary ammonium compound having the formula 1,2-di(acyloxy)-3-trimethylammoniopropane chloride.
[0063] The cationic surfactant useful herein can be one cationic surfactant or a mixture of two or more cationic surfactants.Preferably, the cationic surfactant can be selected from the group consisting of mono-long chain alkyl quaternary ammonium salt; the combination of mono-long chain alkyl quaternary ammonium salt and di-long chain alkyl quaternary ammonium salt; mono-long chain alkyl amine; the combination of mono-long chain alkyl amine and di-long chain alkyl quaternary ammonium salt, and the combination of mono-long chain alkyl amine and mono-long chain alkyl quaternary ammonium salt.
[0064] Mono-long chain alkylamines useful herein are those having one long alkyl chain, preferably 12-30 carbon atoms, more preferably 16-24 carbon atoms, and even more preferably 18-22 alkyl groups. Mono-long chain alkylamines useful herein also include mono-long chain alkyl amidoamines. Primary, secondary, and tertiary aliphatic amines are useful.
[0065] Tertiary amidoamines having an alkyl group of about 12 to about 22 carbons are particularly useful. Exemplary tertiary amidoamines include stearamidopropyl dimethylamine, stearamidopropyl diethylamine, stearamidoethyl diethylamine, stearamidoethyl dimethylamine, palmitamidopropyl dimethylamine, palmitamidopropyl diethylamine, palmitamidoethyl diethylamine, palmitamidoethyl dimethylamine, behenamidopropyl dimethylamine, behenamidopropyl diethylamine, behenamidoethyl diethylamine, behenamidoethyl dimethylamine, arachidamidopropyl dimethylamine, arachidamidopropyl diethylamine, arachidamidoethyl diethylamine, arachidamidoethyl dimethylamine, diethylaminoethyl stearamide. Amines useful in the present invention are disclosed in U.S. Pat. No. 4,275,055 (Nachtigal et al.).
[0066] These amines may be used in combination with acids such as l-glutamic acid, lactic acid, hydrochloric acid, malic acid, succinic acid, acetic acid, fumaric acid, tartaric acid, citric acid, l-glutamic acid hydrochloride, maleic acid, and mixtures thereof, more preferably l-glutamic acid, lactic acid, citric acid, etc., in a molar ratio of amine to acid of about 1:0.3 to about 1:2, more preferably about 1:0.4 to about 1:1.
[0067] Mono long chain alkyl quaternized ammonium salts useful herein are those having one long alkyl chain having 12-30 carbon atoms, preferably 16-24 carbon atoms, more preferably a C18-22 alkyl group. The remaining groups attached to the nitrogen are independently selected from alkyl groups of 1 to about 4 carbon atoms, or alkoxy, polyoxyalkylene, alkylamido, hydroxyalkyl, aryl, or alkylaryl groups having up to about 4 carbon atoms.
[0068] The mono long chain alkyl quaternized ammonium salts useful herein are those having the formula:
[0069] [ka] In the formula, R 75 , R 76 , R 77 , and R 78 is selected from an alkyl group having 12 to 30 carbon atoms, or an aromatic group having up to about 30 carbon atoms, an alkoxy group, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group; R 75 , R 76 , R 77 , and R 78 the remainder are independently selected from an alkyl group of 1 to about 4 carbon atoms, or an alkoxy group having up to about 4 carbon atoms, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group; and X - is a salt-forming anion, such as one selected from halogens (e.g., chloride, bromide), acetate, citrate, lactate, glycolate, phosphate, nitrate, sulfonate, sulfate, alkyl sulfate, and alkyl sulfonate radicals. The alkyl groups may contain, in addition to carbon and hydrogen atoms, ether and / or ester linkages, as well as other groups such as amino groups. Longer chain alkyl groups, e.g., those having about 12 carbon atoms or more, may be saturated or unsaturated. Preferably, R75 , R 76 , R 77 , and R 78 is selected from alkyl groups having 12 to 30 carbon atoms, more preferably 16 to 24 carbon atoms, even more preferably 18 to 22 carbon atoms, and still more preferably 22 carbon atoms; 75 , R 76 , R 77 , and R 78 The remainder is CH 3 , C 2 H 5 , C 2 H 4 OH, and mixtures thereof; X is independently selected from Cl, Br, CH 3 OSO 3 , C 2 H 5 OSO 3 and mixtures thereof.
[0070] Non-limiting examples of such mono-long chain alkyl quaternized ammonium salt cationic surfactants include behenyltrimethylammonium salts, stearyltrimethylammonium salts, cetyltrimethylammonium salts, and hydrogenated tallowalkyltrimethylammonium salts.
[0071] When used, the di-long chain alkyl quaternized ammonium salt may be combined with the mono-long chain alkyl quaternized ammonium salt and / or the mono-long chain alkyl amine salt in a weight ratio of preferably 1:1 to 1:5, more preferably 1:1.2 to 1:5, and even more preferably 1:1.5 to 1:4, from the viewpoint of the stability of the rheological effect and the conditioning effect.
[0072] Di-long chain alkyl quaternized ammonium salts useful herein are those having two long alkyl chains of 12 to 30 carbon atoms, more preferably 16 to 24 carbon atoms, and even more preferably 18 to 22 carbon atoms. Such di-long chain alkyl quaternized ammonium salts useful herein are those having the formula:
[0073] [ka] In the formula, R 71 , R 72 , R 73 , and R 74 two of R are selected from an aliphatic group having 12 to 30 carbon atoms, preferably 16 to 24 carbon atoms, more preferably 18 to 22 carbon atoms, or an aromatic group having up to about 30 carbon atoms, an alkoxy group, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group; 71 , R 72 , R 73 , and R 74 the remainder are independently selected from an aliphatic group of 1 to about 8 carbon atoms, preferably 1 to 3 carbon atoms, or an aromatic group having up to about 8 carbon atoms, an alkoxy group, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group; and X - is a salt-forming anion selected from the group consisting of halides (e.g., chloride and bromide), C1-C4 alkyl sulfates (e.g., methosulfate and ethosulfate), and mixtures thereof. The aliphatic groups may contain, in addition to carbon and hydrogen atoms, ether linkages, and other groups such as amino groups. The longer chain aliphatic groups, e.g., those having about 16 carbon atoms or more, may be saturated or unsaturated. Preferably, R 71 , R 72 , R 73 , and R 74 two of R are selected from alkyl groups having 12 to 30 carbon atoms, preferably 16 to 24 carbon atoms, more preferably 18 to 22 carbon atoms; 71 , R 72 , R 73 , and R 74 The remainder of the 3 , C 2 H 5 , C 2 H 4 OH, CH 2 C 6 H 5and mixtures thereof.
[0074] Such preferred di-long-chain alkyl cationic surfactants include, for example, dialkyl(14-18)dimethylammonium chloride, ditallowalkyldimethylammonium chloride, dihydrogenated tallowalkyldimethylammonium chloride, distearyldimethylammonium chloride, and dicetyldimethylammonium chloride.
[0075] 4. Additional Ingredients In addition to the above-mentioned components, such as water-soluble polymers, plasticizers, and cationic surfactants, the solid sheet article may contain one or more additional components depending on its intended use. In particular, additional components may be present in the solid sheet and / or coating composition. Such one or more additional components may include additional surfactants; perfumes (including encapsulated perfumes or perfume microcapsules), silicones, emulsifiers, solvents (e.g., linear or branched lower C 1 ~C 8 Alcohol, diol, glycerol, or glycol; C 1 ~C 4 lower amine solvents such as alkanolamines, and mixtures thereof; more specifically, 1,2-propanediol, ethanol, glycerol, monoethanolamine, and triethanolamine), carriers, hydrotropes, builders, chelating agents, dispersants, enzymes and enzyme stabilizers, catalytic materials, bleaching agents (including photobleaches) and bleach activators, colorants (such as pigments and dyes, including hueing dyes), brighteners, dye transfer inhibitors, clay soil removal / anti-redeposition agents, structurants, rheology modifiers, foam suppressors, processing aids, antimicrobial agents, non-film forming polymers, foam inhibitors, defoamers, and the like.
[0076] Additional Surfactants Suitable additional surfactants for use in the solid sheet article include anionic surfactants, nonionic surfactants, zwitterionic surfactants, amphoteric surfactants, or combinations thereof. The one or more additional surfactants may be present in an amount of about 0% to about 25%, preferably about 0% to about 15%, such as about 0.1%, about 1%, about 3%, about 5%, about 7%, about 10%, or any range therebetween, of the total weight of the solid sheet article. The additional surfactant may be present in the solid sheet, in the coating composition between the solid sheets, or both.
[0077] Non-limiting examples of anionic surfactants suitable for use herein include alkyl and alkyl ether sulfates, sulfated monoglycerides, sulfonated olefins, alkylarylsulfonates, primary or secondary alkane sulfonates, alkyl sulfosuccinates, acyltaurates, acylisethionates, alkylglyceryl ether sulfonates, sulfonated methyl esters, sulfonated fatty acids, alkyl phosphates, acyl glutamates, acylsarcosinates, alkyl sulfoacetates, acylated peptides, alkyl ether carboxylates, acyllactylates, anionic fluorosurfactants, sodium lauroyl glutamate, and combinations thereof.Preferably, suitable anionic surfactants include C 6 ~C 20 Linear alkylbenzene sulfonates (LAS); sodium trideceth sulfate (STS) with a weight average degree of alkoxylation ranging from about 0.5 to about 5; non-alkoxylated C 6 ~C 20 Linear or branched chain alkyl sulfate; C 6 ~C 20 Linear or branched alkyl alkoxy sulfate (AAS); general formula [R 1 -SO 3 A water-soluble salt of an organic sulfuric acid reaction product of 1 is selected from the group consisting of straight or branched chain saturated aliphatic hydrocarbon radicals having from about 6 to about 20, preferably from about 10 to about 18, carbon atoms, and M is a cation; β-alkyloxyalkanesulfonates.
[0078] Non-limiting examples of non-ionic surfactants suitable for use herein include, but are not limited to, alkyl alkoxylated alcohols, alkyl alkoxylated phenols, alkyl polysaccharides (especially alkyl glucosides and alkyl polyglucosides), polyhydroxy fatty acid amides, alkoxylated fatty acid esters, sucrose esters, sorbitan esters and alkoxylated derivatives of sorbitan esters, amine oxides, etc. Preferred non-ionic surfactants are represented by the formula R 1 (OC 2 H 4 ) n OH (in the formula, R 1 is C 8 ~C 18 and n is an alkyl or alkylphenyl group, and n is from about 1 to about 80. Particularly preferred are C nonionic surfactants having a weight average degree of ethoxylation of from about 1 to about 20, preferably from about 5 to about 15, and more preferably from about 7 to about 10, such as NEODOL® nonionic surfactants available from Shell. 8 ~C 18 Other non-limiting examples of nonionic surfactants useful herein include C alkoxylates, in which the alkoxylate units can be ethyleneoxy units, propyleneoxy units, or mixtures thereof. 6 ~C 12 Alkylphenol alkoxylates; Ethylene oxide / propylene oxide block polymers; C 12 ~C 18 Alcohol and C 6 ~C 12 Alkylphenol condensates (e.g., Pluronic® available from BASF; C 14 ~C 22 Medium-chain branched alcohol (BA); C 14 ~C 22 Medium Branched Chain Alkyl Alkoxylate, BAE x(wherein x is 1-30); alkyl polysaccharides, specifically alkyl polyglycosides; polyhydroxy fatty acid amides; and ether-terminated poly(oxyalkylated) alcohol surfactants. Suitable nonionic surfactants also include those sold by BASF under the trade name Lutensol®. In a preferred embodiment, the nonionic surfactant selected from sorbitan esters and alkoxylated derivatives of sorbitan esters includes sorbitan monolaurate (SPAN® 20), sorbitan monopalmitate (SPAN® 40), sorbitan monostearate (SPAN® 60), sorbitan tristearate (SPAN® 65), sorbitan monooleate (SPAN® 80), sorbitan trioleate (SPAN® 85), sorbitan isostearate, polyoxyethylene(20) sorbitan monolaurate (Tween® 20), Polyoxyethylene (20) sorbitan monopalmitate (Tween® 40), polyoxyethylene (20) sorbitan monostearate (Tween® 60), polyoxyethylene (20) sorbitan monooleate (Tween® 80), polyoxyethylene (4) sorbitan monolaurate (Tween® 21), polyoxyethylene (4) sorbitan monostearate (Tween® 61), polyoxyethylene (5) sorbitan monooleate (Tween® 81), all available from Uniqema, and combinations thereof.
[0079] The most preferred nonionic surfactants for the practice of the present invention are C 6 ~C 20 Linear or branched alkyl alkoxylated alcohols (AA), more preferably C having a weight average degree of alkoxylation in the range of 7 to 9. 12 ~C 14 Linear ethoxylated alcohols include, for example, AE7 and AE9.
[0080] Surprisingly, the presence of nonionic surfactant in the solid sheet can result in an improved dissolution profile. In a preferred but not required embodiment, the solid sheet article can include about 0.01% to about 20%, preferably about 0.1% to about 12%, more preferably about 0.5% to about 8%, most preferably about 1% to about 5%, such as about 0.01%, about 0.1%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 10%, about 12%, about 15%, or any range therebetween, of the total weight of the solid sheet article. Furthermore, the inventors of the present invention have discovered that too much amount of nonionic surfactant (e.g., more than about 10%, 7%, or 5%) can impair the function of the cationic surfactant (e.g., function as a fabric softener) to some extent. Thus, when the nonionic surfactant is present in the most preferred range of amounts, for example, from about 1% to about 5%, a perfect balance between improved dissolution and cationic surfactant functionality can be achieved.
[0081] Amphoteric surfactants suitable for use in the solid sheet articles of the present invention can be broadly described as derivatives of aliphatic secondary and tertiary amines, where the aliphatic radical may be straight or branched, one of the aliphatic substituents containing from about 8 to about 18 carbon atoms and one containing an anionic water-solubilizing group such as carboxy, sulfonate, sulfate, phosphate or phosphonate. Examples of compounds falling within this definition are sodium 3-dodecylaminopropionate, sodium 3-dodecylaminopropanesulfonate, sodium lauryl sarcosinate, N-alkyltaurines such as those prepared by reacting dodecylamine with sodium isethionate, and N-higher alkyl aspartic acids.
[0082] Suitable zwitterionic surfactants include those broadly described as derivatives of aliphatic quaternary ammonium, phosphonium and sulfonium compounds, in which the aliphatic radicals can be straight or branched chain, one of the aliphatic substituents containing from about 8 to about 18 carbon atoms and one containing an anionic group, such as a carboxy, sulfonate, sulfate, phosphate or phosphonate. Such suitable zwitterionic surfactants can be represented by the formula:
[0083] [ka] In the formula, R 2 contains an alkyl, alkenyl, or hydroxyalkyl radical of about 8 to about 18 carbon atoms, 0 to about 10 ethylene oxide moieties, and 0 to about 1 glyceryl moiety; Y is selected from the group consisting of nitrogen, phosphorus, and sulfur atoms; R 3 is an alkyl or monohydroxyalkyl group containing from about 1 to about 3 carbon atoms, X is 1 when Y is a sulfur atom and is 2 when Y is a nitrogen or phosphorus atom, R 4 is an alkylene or hydroxyalkylene of about 1 to about 4 carbon atoms and Z is a radical selected from the group consisting of carboxylate, sulfonate, sulfate, phosphonate, and phosphate groups.
[0084] In some embodiments, the additional surfactant is C 6 ~C 20 Linear alkylbenzene sulfonates (LAS), C with weight average degree of alkoxylation ranging from 0.5 to 10 6 ~C 20 Linear or branched chain alkyl alkoxy sulfates (AAS), C having a weight average degree of alkoxylation ranging from 5 to 15 6 ~C 20 Linear or branched alkyl alkoxylated alcohols (AA), C 6 ~C 20The alkyl group may be selected from the group consisting of linear or branched chain alkyl sulfates (AS), alkyl sulfates, alkyl ether sulfates, alkyl amphoacetates, and any combination thereof.
[0085] fragrance The solid sheet article of the present invention may contain a fragrance. Preferably, the solid sheet article may contain about 0.01% to about 50%, preferably about 0.02% to about 30%, more preferably about 0.1% to about 20%, for example, about 0.01%, about 0.02%, about 0.05%, about 0.1%, about 0.2%, about 0.3%, about 0.5%, about 1%, about 2%, about 3%, about 5%, about 10%, or any range therebetween, of the fragrance by total weight of the solid sheet article.
[0086] In particular, the perfume may be present in the solid sheet and / or coating composition. Preferably, the perfume may be free perfume, perfume microcapsules, or any combination thereof. In particular, the coating composition may comprise 1% to 99% by weight, preferably 5% to 90% by weight, more preferably 10% to 80% by weight, for example, 1%, 2%, 3%, 4%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% by weight, or any range therebetween, based on the total weight of the coating composition.
[0087] In some embodiments, at least 50%, preferably at least 70%, more preferably at least 90%, and most preferably at least 99% of the perfume in a solid article according to the present disclosure is present in the coating composition, which may provide improved perfume performance, such as longevity, perfume stability, deposition, or release benefits.
[0088] silicone The solid sheet article of the present invention may contain silicone, preferably organosilicone. Preferably, the solid sheet article may contain about 0.01% to about 50%, preferably about 0.1% to about 30%, more preferably about 1% to about 20%, such as about 1%, about 2%, about 3%, about 5%, about 7%, about 10%, about 15%, about 20%, or any range therebetween, of the total weight of the solid sheet article. When the solid sheet article of the present invention is used as a fabric conditioning product, the silicone may function as a co-softening agent.
[0089] In particular, silicone may be present in the solid sheet and / or coating composition. Preferably, the coating composition may comprise about 0.01% to about 100%, preferably about 0.1% to about 99.9%, more preferably about 1% to about 99% of the total weight of the coating composition, such as about 1%, about 5%, about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90%, about 95%, or any range therebetween.
[0090] Preferably, suitable organosilicones may contain Si-O moieties and may be selected from (a) non-functionalized siloxane polymers, (b) functionalized siloxane polymers, and mixtures thereof. The molecular weight of the organosilicon is usually indicated with reference to the viscosity of the material. In one embodiment, the organosilicon may have a viscosity of about 10 to about 2,000,000 centistokes at 25°C. In another embodiment, suitable organosilicones may have a viscosity of about 10 to about 800,000 centistokes at 25°C.
[0091] Suitable organosilicones may be linear, branched, or crosslinked, and suitable examples are described in U.S. Pat. Nos. 6,815,069, 7,153,924, 7,321,019, and 7,427,648, and U.S. patent application Ser. No. 61 / 319939.
[0092] In some embodiments, the silicone may be selected from the group consisting of vinyl dimethicone / methicone silsesquioxane crosspolymer, polysilicone, polymethylsilsesquioxane, diphenyl dimethicone / vinyl diphenyl dimethicone / silsesquioxane crosspolymer, and any combination thereof.
[0093] solvent Other optional components in the solid sheet article may include solvents, particularly water-miscible solvents and co-solvents useful as solubilizers for polymeric structurants and as drying promoters. In particular, solvents may be present in the solid sheet and / or coating composition. Non-limiting examples of suitable solvents include alcohols, esters, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, and combinations thereof. Alcohols and esters are more preferred. Preferred alcohols are monohydric. Most preferred monohydric alcohols are ethanol, isopropanol, and n-propanol. Most preferred esters are ethyl acetate and butyl acetate. Other non-limiting examples of suitable organic solvents are benzyl alcohol, amyl acetate, propyl acetate, acetone, heptane, isobutyl acetate, isopropyl acetate, toluene, methyl acetate, isobutanol, n-amyl alcohol, n-butyl alcohol, hexane, and methyl ethyl ketone, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, methyl ethyl ketone, acetone, and combinations thereof.
[0094] In some embodiments, the solvent may be selected from the group consisting of glycerol, propylene glycol, 1,3-propanediol, diethylene glycol, dipropylene glycol, ethanolamine, ethanol, water, and any combination thereof.
[0095] Adhesion aid In one embodiment, the solid sheet article may include from about 0.01% to about 20%, from about 0.1 to about 15%, or from about 0.2 to about 10% of the total weight of the solid sheet article of a deposition aid. In particular, the deposition aid may be present in the solid sheet and / or coating composition. Suitable deposition aids are disclosed, for example, in U.S. Patent Application Serial No. 12 / 080,358.
[0096] In one embodiment, the deposition aid may be a cationic or amphoteric polymer. In one embodiment, the deposition aid may be a cationic polymer. Cationic polymers in general, and methods for their preparation, are known in the literature. In one embodiment, the cationic polymer may have a cationic charge density of about 0.005 to about 23, about 0.01 to about 12, or about 0.1 to about 7 meq / g at the pH of the intended use of the composition. For amine-containing polymers, where the charge density depends on the pH of the composition, the charge density is measured at the pH of the intended use of the product. Such pH is typically in the range of about 2 to about 11, more typically about 2.5 to about 9.5. The charge density is calculated by dividing the number of net charges per repeat unit by the molecular weight of the repeat unit. The positive charges may be located on the backbone of the polymer and / or on the side chains of the polymer. In particular, the cationic polymer may be cationic hydroxyethylcellulose, preferably having a weight average molecular weight of 200 kDa to 600 kDa (e.g., 400 kDa), a charge density of 0.1 to 0.3 (e.g., 0.18), and / or an average weight percentage of nitrogen per anidroglucose repeat unit of 0.2% to 0.4% (e.g., 0.28%).
[0097] One group of suitable cationic polymers includes those produced by polymerization of ethylenically unsaturated monomers with a suitable initiator or catalyst, such as those disclosed in WO 00 / 56849 and U.S. Pat. No. 6,642,200.
[0098] Additional supplemental ingredients In another embodiment, the solid sheet article may further comprise additional auxiliary components. In particular, additional auxiliary components may be present in the solid sheet and / or coating composition. These additional auxiliary components act as processing aids and can modify the properties of the solid sheet article, such as the solubility and dissolution rate, dissolution stability, resistance to moisture absorption during storage, stretchability, feel, brittleness, and texture, appearance and gloss of the substrate, as well as the ease and speed of processing, molding, extrusion, or drying of the substrate, mechanical handling of the article, and storage of the article. Such additional auxiliary components include emulsifiers, non-film-forming polymers, anti-blocking agents, antifoaming agents, defoamers, biocides, preservatives, colorants, opacifiers, pearlescent agents, fillers and extenders, rheology modifiers, and the like.
[0099] The rheology modifier may preferably be selected from the group consisting of cellulose and derivatives; guar and guar derivatives; polyethylene oxide, polypropylene oxide, and POE-PPO copolymers; polyvinylpyrrolidone, crosslinked polyvinylpyrrolidone and derivatives; polyvinyl alcohol and derivatives; polyethyleneimine and derivatives; inorganic particles such as sodium carbonate and sodium sulfate; silicon dioxide; water-swellable clays; gums; and any combination thereof.
[0100] The emulsifier may be selected from the group consisting of mono- and diglycerides, fatty alcohols, polyglycerol esters, propylene glycol esters, sorbitan esters, polyhydroxystearic acid, and any combination thereof.
[0101] The solid sheet articles of the present invention may further comprise other optional ingredients as are known or useful for use in compositions, provided that such optional materials are compatible with the selected essential materials described herein or do not unduly impair product performance.
[0102] III. Process for Making Solid Sheets A process for making a flexible porous dissolvable solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant may include: a) preparing a wet premix comprising a water soluble polymer, a plasticizer, and a cationic surfactant, wherein the weight ratio of plasticizer to cationic surfactant is from about 0.9 to about 2; b) aerating the wet premix to form an aerated wet premix; c) forming the aerated wet premix into a sheet having opposed first and second surfaces; and d) drying the formed sheet to form the sheet article.
[0103] In particular, aeration of the wet premix is performed to introduce a sufficient amount of air bubbles into the wet premix to form an OCF structure therein upon subsequent drying. After being fully aerated, the wet premix is characterized by a density significantly lower than that of a non-aerated wet premix (which may contain a few inadvertently trapped air bubbles) or a poorly aerated wet premix (which may contain some air bubbles, but at a very low volumetric percentage and with significantly larger air bubble sizes). Preferably, the aerated wet premix has a density in the range of about 0.1 g / mL to about 0.7 g / mL, preferably about 0.15 g / mL to about 0.6 g / mL, more preferably about 0.2 g / mL to about 0.5 g / mL, and most preferably about 0.25 g / mL to about 0.45 g / mL.
[0104] Aeration can be achieved by either physical or chemical means in the present invention. In one embodiment, it can be achieved by introducing gas into the wet premix through mechanical agitation, for example, by using any suitable mechanical processing means, including, but not limited to, rotor-stator mixers, planetary mixers, pressurized mixers, non-pressurized mixers, batch mixers, continuous mixers, semi-continuous mixers, high shear mixers, low shear mixers, submerged sparsers, or any combination thereof. In another embodiment, it can be achieved through chemical means, for example, by introducing carbon dioxide (CO) through a foaming system. 2This can be accomplished using chemical blowing agents to provide in situ gas formation via chemical reaction of one or more ingredients, including the formation of a gas. In a particularly preferred embodiment, it has been found that aeration of the wet premix can be cost effectively accomplished by using continuous pressurized aerators or mixers conventionally utilized in the food industry in the manufacture of marshmallows.
[0105] WO 2010 / 077627 discloses a batch process for forming a porous sheet having an open cell foam (OCF) structure characterized by an open cell content percentage of about 80%-100% that functions to improve dissolution. Specifically, a premix of raw materials is first formed, which is vigorously aerated and then thermally dried in batch (e.g., in a convection oven or microwave oven) to form a porous sheet having the desired OCF structure. Although such an OCF structure significantly improves the dissolution rate of the resulting porous sheet, there are still visually denser, less porous bottom regions within such sheets, with thicker cell walls. Such dense bottom regions can adversely affect the flow of water through the sheet, thereby adversely affecting the overall dissolution rate of the sheet. When multiple such sheets are laminated together to form a multi-layer structure, the "barrier" effect of the multiple dense bottom regions is particularly enhanced.
[0106] WO 2012 / 138820 discloses a process similar to that of WO 2010 / 077627, except that continuous drying of the aerated wet premix is achieved by using, for example, an impingement oven (instead of a convection oven or a microwave oven). The OCF sheet formed by such a continuous drying process is characterized by improved uniformity / consistency in the pore structure across its different regions. Unfortunately, such OCF sheets still have rate-limiting factors, such as a top surface with relatively small pore openings and an upper region with relatively small pores (i.e., a crust-like upper region), which can adversely affect the flow of water passing therethrough and slow down its dissolution.
[0107] During the drying step in the above process, the OCF structure is formed under the simultaneous mechanisms of water evaporation, bubble collapse, interstitial liquid drainage from the thin film bubble surfaces into the plateau boundaries between the bubbles (creating openings between the bubbles to form open cells), and premix solidification. Various processing conditions can affect these mechanisms, such as, for example, solids content in the wet premix, viscosity of the wet premix, gravity, and drying temperature, as well as the need to balance such processing conditions to achieve controlled drainage to form the desired OCF structure.
[0108] In addition to the processing conditions described above, it was a surprising and unexpected discovery that the direction of the thermal energy used during the drying process (ie, heating direction) can also have a significant effect on the resulting OCF structure.
[0109] For example, when thermal energy is applied to a non-directional material (i.e., there is no clear heating direction) during the drying process, or when the heating direction is substantially aligned with the gravity direction (i.e., the offset angle between them is less than 90°) throughout the majority of the drying process, the resulting flexible porous dissolvable solid sheet tends to have a top surface with smaller pore openings and greater pore size variation in different regions along the direction through its thickness. In contrast, when the heating direction is offset from the gravity direction (i.e., with an offset angle of 90° or more between them) throughout the majority of the drying process, the resulting solid sheet may have a top surface with larger pore openings and reduced pore size variation in different regions along the direction through the thickness of such sheet. Correspondingly, the latter sheet is more receptive to water flowing therethrough, and therefore more soluble, than the former sheet.
[0110] Without wishing to be bound by any theory, it is believed that the alignment or misalignment between the heating direction and the gravity direction during the drying process, and its duration, can significantly affect the interstitial liquid evacuation between the gas bubbles, which in turn can affect the pore expansion and pore opening in the solidified premix, resulting in solid sheets with very different OCF structures. Such differences are more clearly shown in Figures 1-4 below.
[0111] FIG. 1 shows a convection heating / drying configuration. During the drying process, a mold 10 (which may be made of any suitable material, such as metal, ceramic, or Teflon®) is filled with the aerated wet premix, which forms a sheet 12 having a first surface 12A (i.e., the top surface) and an opposing second surface 12B (i.e., the bottom surface since it is in direct contact with the support surface of the mold 10). Such a mold 10 is placed in a convection oven at 130° C. for about 45-46 minutes during the drying process. The convection oven heats the sheet 12 from above, i.e., along a downward heating direction (as indicated by the cross-hatched arrows), which creates a decreasing temperature gradient within the sheet 12 from the first surface 12A to the opposing second surface 12B. The downward heating direction is aligned with the gravity direction (as indicated by the white arrow), and such aligned position is maintained throughout the drying time. During drying, gravity drains the liquid premix downwards towards the bottom region, while the downward heating direction causes the top region to dry first and the bottom region to dry last. As a result, a porous solid sheet is formed with a top surface that contains many pores with small openings formed by bubbles that have not had the chance to fully expand. Such a top surface with smaller pore openings is not optimal for water penetration into the sheet, which may limit the dissolution rate of the sheet. Meanwhile, the bottom region of such a sheet is denser and less porous, with a very small number of larger pores formed by fully expanded bubbles, and the bubble walls between the pores in such a bottom region are thicker due to the downward liquid drainage caused by gravity. Such a dense bottom region with fewer pores and thick bubble walls is an additional rate limiting factor for the overall dissolution rate of the sheet.
[0112] FIG. 2 shows a microwave heating / drying configuration. During the drying process, a mold 30 is filled with aerated wet premix, which forms a sheet 32 having a first surface 32A (top surface) and an opposing second surface 32B (bottom surface). Such a mold 30 is then placed in a low energy density microwave applicator (not shown) provided by Industrial Microwave Systems Inc. (North Carolina) and operated at a power of 2.0 kW, a belt speed of 1 ft / min, and an ambient air temperature of 54.4° C. The mold 30 is left under such microwave application for about 12 minutes during the drying process. Such a microwave applicator heats the sheet 32 from the inside without any clear or consistent heating direction. Correspondingly, no temperature gradient is formed in the sheet 32. During drying, the entire sheet 32 is heated simultaneously or nearly simultaneously, but gravity (as indicated by the white arrow) still drains the liquid premix downward toward the bottom region. As a result, the solidified sheet so formed has more evenly distributed and more uniformly sized pores compared to sheets formed by convection heating / drying configurations. However, liquid drainage under gravity during the microwave drying process may still result in dense bottom regions with thick cell walls. Furthermore, simultaneous heating of the entire sheet 32 may still limit pore expansion and pore opening at the top surface during the drying process, and the resulting sheet may still have a top surface with relatively small pore openings. Furthermore, microwave energy may heat water within the sheet 32, causing such water to boil and generating irregularly sized bubbles, forming unintended dense regions with thick cell walls.
[0113] FIG. 3 shows an impingement oven heating / drying configuration. During the drying process, a mold 40 is filled with aerated wet premix, which forms a sheet 42 having a first surface 42A (top surface) and an opposing second surface 42B (bottom surface). Such a mold 40 is then placed in a continuous impingement oven (not shown) under conditions similar to those described in Example 1, Table 2 of WO2012138820. Such a continuous impingement oven heats the sheet 42 from both the top and bottom with opposing and offset heating directions (as indicated by the two cross-hatched arrows). Correspondingly, no significant temperature gradient is formed within the sheet 42 during drying, and the entire sheet 42 is heated from both its top and bottom surfaces at approximately the same time. Similar to the microwave heating / drying configuration described in FIG. 3, gravity (as indicated by the white arrow) continues to drain the liquid premix downwards toward the bottom region in such an impingement oven heating / drying configuration of FIG. 4. As a result, the solidified sheet so formed has more evenly distributed and more uniformly sized pores compared to sheets formed by convection heating / drying configurations. However, liquid drainage under gravity during the drying process may still result in a dense bottom region with thick cell walls. Furthermore, the nearly simultaneous heating of the sheet 42 from both sides may still limit pore expansion and pore opening at the top surface during the drying process, and the resulting sheet may still have a top surface with relatively small pore openings.
[0114] In addition to the heating / drying configurations mentioned above (convection, microwave or impingement oven), the present invention provides another heating / drying configuration for drying an aerated wet pre-mix in which the direction of heating is purposefully configured to impede / reduce gravity-driven liquid drainage towards the bottom region (thereby reducing density and improving pore structure in the bottom region) and to allow more time for gas bubbles near the top surface to expand during drying (thereby creating significantly larger pore openings at the top surface of the resulting sheet). Both of these features function to improve the overall dissolution rate of the sheet and are therefore desirable.
[0115] FIG. 4 illustrates a bottom conduction heating / drying setup for making flexible porous dissolvable sheets according to one embodiment of the present invention. Specifically, a mold 50 is filled with an aerated wet premix, which forms a sheet 52 having a first side 52A (i.e., bottom side) and an opposing second side 52B (i.e., top side). Such a mold 50 is placed on a heated surface (not shown), for example a pre-heated Peltier plate having a controlled surface temperature of about 125-130° C., for about 30 minutes during the drying process. Heat is conducted from the heated surface at the bottom of the mold 50 through the mold, heating the sheet 52 from below, i.e., along an upward heating direction (as indicated by the cross-hatched arrows), which creates a decreasing temperature gradient within the sheet 52 from the first side 52A (bottom side) to the opposing second side 52B (top side). Such upward heating direction is opposite to the direction of gravity (as indicated by the white arrow) and is maintained as such throughout the entire drying time (i.e., the heating direction is opposite to the direction of gravity for nearly 100% of the drying time). During drying, gravity still drains the liquid premix downward toward the bottom region. However, the upward heating direction dries the sheet from bottom to top, and since the heat-generated water vapor in the bottom region rises upward to escape the solidified matrix, downward liquid drainage toward the bottom region is significantly restricted and "impeded" / reduced by the solidified matrix and the rising water vapor. Correspondingly, the bottom region of the resulting dried sheet is less dense and contains a large number of pores with relatively thin cell walls. Furthermore, since the top region is the last region to be dried during the process, the air bubbles in the top region have enough time to expand to form sizable open pores on the top surface of the resulting sheet, which is particularly effective in promoting water ingress into the sheet. Additionally, the resulting sheet has a more even distribution of overall pore sizes throughout its different regions (eg, top, middle, bottom).
[0116] FIG. 5 illustrates a rotating drum heating / drying configuration for making flexible porous dissolvable sheets according to another embodiment of the present invention. Specifically, a feed trough 60 is filled with an aerated wet premix 61. A heated rotatable cylinder 70 (also referred to as a drum dryer) is positioned above the feed trough 60. The heated drum dryer 70 has a cylindrical heated outer surface characterized by a controlled surface temperature of about 130° C., which rotates along a clockwise direction (as indicated by the thin curve with an arrow) to pick up the aerated wet premix 61 from the feed trough 60. The aerated wet premix 61 forms a thin sheet 62 on the cylindrical heated outer surface of the drum dryer 70, and such sheet 62 of the aerated wet premix is rotated and dried for about 10-15 minutes. To ensure a consistent thickness of the sheet 62 thus formed, the thickness of the sheet 62 can be controlled by simply adjusting the viscosity of the aerated wet premix 61 and the rotational speed and surface temperature of the drum dryer 70, although a leveling blade (not shown) may be positioned near the slurry pick-off location. Once dried, the sheet 62 can be picked off manually or by a scraper 72 at the end of the drum rotation.
[0117] As shown in FIG. 5, the sheet 62 formed by the aerated wet premix 61 includes a first surface 62A (i.e., bottom surface) that is in direct contact with the heated exterior surface of the heated drum dryer 70, and an opposing second surface 62B (i.e., top surface). Correspondingly, heat from the drum dryer 70 is conducted to the sheet 62 along an outward heating direction, first heating the first surface 62A (bottom surface) of the sheet 62, and then heating the opposing second surface 62B (top surface). Such an outward heating direction creates a temperature gradient within the sheet 62 that decreases from the first surface 62A (bottom surface) to the opposing second surface 62B (top surface). The outward heating direction slowly and constantly changes as the drum dryer 70 rotates, along a very distinct and predictable path (as shown by the multiple outwardly extending cross-hatched arrows in FIG. 4). The relative positions of the outward heating direction and the gravity direction (as indicated by the white arrows) also decelerate and constantly change in a similarly distinct and predictable manner. For less than half of the drying time (i.e., when the heating direction is below the horizontal dashed line), the outward heating direction is substantially aligned with the gravity direction with an offset angle of less than 90° between them. For the majority of the drying time (i.e., when the heating direction is at or above the horizontal dashed line), the outward heating direction is opposite or substantially opposite the gravity direction with an offset angle of 90° or more between them. Depending on the initial "start" coating location of the sheet 62, the heating direction can be opposite or substantially opposite the gravity direction for more than 55% of the drying time (if coating begins just at the bottom of the drum dryer 70) and preferably for more than 60% of the drying time (if coating begins higher up on the drum dryer 70 as shown in FIG. 5). As a result, during most of the drying process, this slow rotation and change in heating direction in the rotating drum heating / drying configuration can still function to limit and "block" / reduce gravity-induced liquid drainage within the sheet 62, resulting in improved OCF structure in the sheet so formed.The resulting sheet after drying with the heated drum dryer 70 is also characterized by a less dense bottom region having a greater number of more uniformly sized pores and a top surface having relatively larger pore openings. Additionally, the resulting sheet has a more uniform distribution of overall pore size throughout its different regions (e.g., top, middle, bottom).
[0118] IV. Physical Properties of the Solid Sheet Articles of the Present Invention The flexible porous dissolvable solid sheet articles of the present invention are characterized by an improved pore structure that allows for easier water ingress into the sheet article and faster dissolution of the sheet article in water.
[0119] In general, such solid sheet articles may be characterized by (i) a percent open cell content of about 80%-100%, preferably about 85%-100%, more preferably about 90%-100%, as measured by Test 3 below, and (ii) an overall average pore size of about 100 μm to about 2000 μm, preferably about 150 μm to about 1000 μm, more preferably about 200 μm to about 600 μm, as measured by the Micro-CT method described in Test 2 below. The overall average pore size defines the porosity of the OCF structure of the present invention. The percent open cell content defines the interconnectivity between the pores in the OCF structure of the present invention. The interconnectivity of the OCF structure may also be described by the star volume or Structure Model Index (SMI) as disclosed in WO 2010 / 077627 and WO 2012 / 138820.
[0120] Such solid sheet articles of the present invention have opposed top and bottom surfaces, the top surface of which may be characterized by a surface average pore size, as measured by the SEM method described in Test 1 below, of greater than about 300 μm, preferably greater than about 310 μm, preferably greater than about 320 μm, more preferably greater than about 330 μm, and most preferably greater than about 350 μm.
[0121] Furthermore, the solid sheet article of the present invention may be characterized by a uniform pore size distribution among different regions along its thickness. Specifically, the solid sheet article of the present invention includes a top region adjacent to the top surface, a bottom region adjacent to the bottom surface, and a middle region therebetween, the top region, middle region, and bottom region all having the same thickness. Each of the top region, middle region, and bottom region of such a solid sheet article is characterized by an average pore size, and the ratio of the average pore size in the bottom region to the average pore size in the top region (i.e., bottom-to-top average pore size ratio) may be about 0.6 to about 1.5, preferably about 1 to about 1.2. Furthermore, the solid sheet article of the present invention may be characterized by a bottom-to-middle average pore size ratio of about 0.5 to about 1.5, preferably about 0.9 to about 1.1, and a middle-to-top average pore size ratio of about 1 to about 1.5, preferably about 1 to about 1.2.
[0122] Preferably, the solid sheet articles of the present invention are further characterized by an average cell wall thickness of from about 5 μm to about 200 μm, preferably from about 10 μm to about 100 μm, and more preferably from about 10 μm to about 80 μm, as measured by Test 2 below.
[0123] The solid sheet article of the present invention may contain small amounts of water, and is preferably characterized by a final moisture content of from about 0.5% to about 25%, preferably from about 1% to about 20%, and more preferably from about 3% to about 15%, by weight of the solid sheet article, as determined by Test 4 below.
[0124] Each sheet of the solid sheet article of the present invention may have a thickness ranging from about 0.6 mm to about 3.5 mm, preferably from about 0.7 mm to about 3 mm, more preferably from about 0.8 mm to about 2 mm, and most preferably from about 1 mm to about 1.5 mm. The thickness of the solid sheet article may be measured using Test 6 described below.
[0125] The solid sheet article of the present invention has a hardness of about 50 grams / m2 as measured by Test 6 described below. 2 ~ approx. 250g / m 2 , preferably about 80 g / m2 ~ approx. 230g / m 2 , more preferably about 100 grams / m 2 ~ approx. 220g / m 2 The sheet may be further characterized by its basis weight.
[0126] Furthermore, the solid sheet articles of the present invention have a compressibility of about 0.05 grams / cm as measured by Test 7 below. 3 ~ approx. 0.5g / cm 3 , preferably about 0.06 g / cm 3 ~ approx. 0.4g / cm 3 , more preferably about 0.07 grams / cm 3 ~ approx. 0.3 g / cm 3 , and most preferably about 0.08 grams / cm 3 ~ approx. 0.25g / cm 3 The density of the solid sheet article of the present invention may be lower than the density of a sheet of aerated wet premix due in part to pore expansion which results in an overall volume expansion.
[0127] Additionally, the solid sheet articles of the present invention have a hardness of less than about 0.03 m, as measured by Test 8 described below. 2 / g~approx.0.25m 2 / g, preferably about 0.04m 2 / g~approx.0.22m 2 / g, more preferably 0.05m 2 / g~0.2m 2 / g, most preferably 0.1m 2 / g~0.18m 2 The specific surface area of the solid sheet article of the present invention may be indicative of its porosity and may affect its dissolution rate, e.g., the higher the specific surface area, the more porous the sheet article and the faster its dissolution rate.
[0128] V. Conversion of multiple sheets into a multi-layer structure Once the flexible dissolvable porous solid sheets of the present invention are formed, two or more of such sheets can be further combined and / or processed as described above to form a dissolvable solid sheet article of any desired three-dimensional shape, including, but not limited to, a sphere, a cube, a rectangle, an oval, a cylinder, a rod, a sheet, a flower, a fan, a star, a disk, etc. The sheets may be combined and / or processed by any means known in the art, including, but not limited to, chemical means, mechanical means, and combinations thereof. Such combining and / or processing steps are collectively referred to herein as a "conversion" process, i.e., which serves to convert two or more flexible dissolvable porous sheets of the present invention into a dissolvable solid sheet article having a desired three-dimensional shape.
[0129] Conventional dissolvable solid articles have a relatively high length / width to thickness ratio, i.e., are relatively thin, to ensure the rapid dissolution of such articles in water.Thus, such dissolvable solid articles are typically provided in the form of relatively large but thin sheet products, which can be difficult to handle (e.g., excessively soft when used, easily stick together and difficult to separate when used), and are not aesthetically pleasing to consumers.However, due to the constraints imposed by dissolution requirements, there is little or no space for changing or improving such product forms.
[0130] It was a surprising and unexpected discovery of the present invention that three-dimensional multi-layer solid articles formed by stacking multiple layers of the solid sheets of the present invention are more soluble than single-layer solid articles having the same aspect ratio, which allows such solid articles to be significantly stretched along their thickness to create three-dimensional product shapes that are easier to handle and more aesthetically pleasing to the consumer (e.g., thick pads or even cube-shaped products).
[0131] Specifically, the multi-layer dissolvable solid article formed by stacking multiple layers of the solid sheet of the present invention is characterized by a maximum dimension D and a minimum dimension z (perpendicular to the maximum dimension), with the D / z ratio (hereinafter also referred to as "aspect ratio") ranging from 1 to about 10, preferably from about 1.4 to about 9, preferably from about 1.5 to about 8, more preferably from about 2 to about 7. It is noted that when the aspect ratio is 1, the dissolvable solid article has a spherical shape. When the aspect ratio is about 1.4, the dissolvable solid article has a cubic shape.
[0132] The multi-layered dissolvable solid articles of the present invention may have a minimum dimension z greater than about 3 mm but less than about 20 cm, preferably from about 4 mm to about 10 cm, and more preferably from about 5 mm to about 30 mm.
[0133] The multi-layered dissolvable solid article described above may comprise two or more such flexible dissolvable porous sheets. For example, it may comprise from about 2 to about 50, preferably from about 3 to about 40, and more preferably from about 4 to about 30 flexible dissolvable porous sheets. The improved OCF structure within the flexible dissolvable porous sheets made according to the present invention allows many sheets (e.g., 15 to 40) to be stacked together while still providing a sufficient overall dissolution rate for the stack.
[0134] Furthermore, the solid sheet article of the present invention may comprise two or more flexible porous dissolvable sheets, and the coating composition is present on at least one surface of at least one of the two or more sheets, provided that the coating composition is not present on any outer surface of the solid sheet article. In other words, one or more functional components can be "sandwiched" between the individual sheets of the multi-layered dissolvable solid article described above. In particular, the coating composition can be applied between the individual sheets of the multi-layered dissolvable solid article by any suitable means, such as spraying, sprinkling, dusting, coating, spreading, dipping, pouring, or even vapor deposition. More specifically, the coating composition can be applied to one or both of the contact surfaces of adjacent sheets in the stack.
[0135] Preferably, as described above, the coating composition may contain silicone and / or other ingredients, such as additional surfactants (e.g., non-ionic surfactants), fragrances, and rheology modifiers. The coating composition is heated at 20° C. and 1 s. -1 The viscosity may be from about 1 cps to about 25,000 cps, preferably from about 2 cps to about 10,000 cps, more preferably from about 3 cps to about 5,000 cps, and most preferably from about 1,000 cps to about 5,000 cps, as measured by a viscosity ratio of 1.0. The viscosity values are measured using a Malvern Kinexus Lab+ rheometer (CP1 / 50 SR3468 SS) with a cone and plate geometry at a gap width of 0.054 mm, a temperature of 20° C., and a shear rate of 1.0 reciprocal seconds for 360 seconds. The surprising and unexpected discovery of the present invention is that a three-dimensional multi-layer solid article containing the coating composition has a significantly improved dissolution profile than a multi-layer solid article having the same amount of active ingredient but not containing the coating composition. Furthermore, a solid sheet article containing the coating composition can provide additional benefits, including improved flexibility and / or anti-wrinkle effects, compared to a solid sheet article not containing the coating composition.
[0136] Moreover, in order for such functional ingredients to not be obstructed by cut seals or edge seals near the periphery of the individual sheets, such functional ingredients are preferably located within a central region between two adjacent sheets, defined as an area spaced from the periphery of such adjacent sheets by a distance of at least 10% of the maximum dimension D. Preferably, the weight ratio of coating composition to sheets in the solid sheet article is from about 0.01 to about 2, preferably from about 0.02 to about 1, more preferably from about 0.05 to about 0.8, and most preferably from about 0.08 to about 0.5, e.g., about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, about 0.1, about 0.15, about 0.2, about 0.3, about 0.4, about 0.5, or any range therebetween.
[0137] Test Method Test 1: Scanning Electron Microscopy (SEM) Method for Determining Surface Average Pore Size of Sheet Articles SEM micrographs of the samples are obtained using a Hitachi TM3000 Tabletop Microscope (S / N: 123104-04). Samples of the solid sheet articles of the present invention are approximately 1 cm x 1 cm in area and are cut from larger sheets. Images are collected at 50X magnification and the unit is operated at 15 kV. A minimum of five microscopic images are collected from randomly selected locations across each sample, resulting in an estimated average pore size of approximately 43.0 mm. 2 Obtain the total analyzed area.
[0138] The SEM micrographs are then first processed using an image analysis toolbox in Matlab®. Images are converted to grayscale if necessary. For a given image, a histogram of intensity values for every single pixel is generated using the Matlab® “imhist” function. Typically, such a histogram reveals two separate distributions, corresponding to the lighter sheet surface pixels and the darker area pixels within the pores. A threshold is selected that corresponds to an intensity value between the peak values of these two distributions. All pixels with intensity values lower than this threshold are then set to an intensity value of 0, and pixels with intensity values higher than it are set to 1, thereby generating a binary black and white image. The binary image is then analyzed using ImageJ (https: / / imagej.nih.gov, version 1.52a) to examine both the pore area ratio and the pore size distribution. The scale bar of each image is used to provide a pixel / mm scaling factor. For analysis, the autothresholding and analyze particles functions are used to isolate each pore. Output from the analysis function includes area ratios for the whole image and pore area, and pore perimeter for each detected pore.
[0139] The average pore size is D A 50, i.e., 50% of the total pore area is D A It is composed of pores having a hydraulic diameter of 50 or less average diameter. Hydraulic diameter='4* Pore area (m 2 ) / pore circumference (m)' This is an equivalent diameter calculated to take into account pores that are not all circular.
[0140] Test 2: Micro-Computed Tomographic (μCT) Method for Determining Whole or Regional Average Pore Size and Average Cell Wall Thickness of Open Cell Foams (OCF) Porosity is the ratio of void space to the total space occupied by the OCF. Porosity can be calculated from a μCT scan by segmenting the void space by thresholding and determining the ratio of void voxels to total voxels. Similarly, solid volume fraction (SVF) is the ratio of solid space to total space, and SVF can be calculated as the ratio of occupied voxels to total voxels. Both porosity and SVF are average scalar values that do not provide structural information such as pore size distribution across the height of the OCF or the average cell wall thickness of the OCF struts.
[0141] To characterize the 3D structure of the OCF, the sample is imaged using a μCT X-ray scanning device capable of acquiring a data set with high isotropic spatial resolution. An example of a suitable instrument is a SCANCO System model 50 μCT scanner (Scanco Medical AG, Bruttisellen, Switzerland) operating with the following settings: Energy level: 45 kVp at 133 μA; projection: 3000; field of view: 15 mm; integration time: 750 ms; average: 5 times; and voxel size: 3 μm per pixel. After the scan and subsequent data reconstruction are completed, the scanner system creates a 16-bit data set, referred to as an ISQ file, in which the gray levels reflect the changes in X-ray attenuation and thus relate to the material density. The ISQ file is then converted to 8-bit using a scaling factor.
[0142] Scanned OCF samples are typically prepared by punching a core approximately 14 mm in diameter. The OCF punch is placed flat on a low damping foam and then mounted into a 15 mm diameter plastic cylindrical tube for scanning. A scan of the sample is acquired such that the entire volume of all mounted cut samples is included in the data set. From this larger data set, smaller sub-volumes of the sample data set are extracted from the total cross-section of the scanned OCF to create a 3D data slab, where the pores can be qualitatively evaluated without edge / boundary effects.
[0143] To characterize the pore size distribution in the height direction, a strut size, local thickness map algorithm, or LTM, is implemented on the subvolume dataset. The LTM method starts with Euclidean Distance Mapping (EDM), assigning each void voxel a gray level value equal to its distance from its nearest boundary. Based on the EDM data, the 3D void space representing the pores (or the 3D solid space representing the struts) is tessellated with spheres sized to match the EDM values. Voxels enclosed by the spheres are assigned the radial value of the largest sphere. In other words, each void voxel (or solid voxel of a strut) is assigned the radial value of the largest sphere that both fits within the void space boundary (or solid space boundary of a strut) and contains the assigned voxel.
[0144] The 3D labeled sphere distribution output from the LTM data scan is processed as a stack of two-dimensional images in the height direction (or Z direction) and can be used to estimate the change in sphere diameter from slice to slice as a function of OCF depth. Strut thickness is processed as a 3D data set and average values can be evaluated for all or part of the subvolume. Calculations and measurements were performed using Thermo Fisher Scientific's AVIZO Lite (9.2.0) and Mathworks' MATLAB (R2017a).
[0145] Test 3: Percentage of Open Cells in Sheet Articles The percent open cell content is measured through gas pycnometry. Gas pycnometry is a common analytical technique that uses gas displacement to accurately measure volume. An inert gas such as helium or nitrogen is used as the displacement medium. A sample of the solid sheet article of the present invention is sealed in an instrument compartment of known volume, charged with the appropriate inert gas, and then expanded to another precise internal volume. The pressure before and after expansion is measured and used to calculate the volume of the sample article.
[0146] ASTM Standard Test Method D2856 provides a procedure for determining the percentage of open cells using an older model of an air comparison pycnometer. This device is no longer manufactured. However, one can conveniently and precisely determine the percentage open cells by performing tests using a Micromeritics AccuPyc Pycnometer. ASTM Procedure D2856 describes five methods (A, B, C, D, and E) for determining the open cell ratio of foamed materials. For these experiments, samples can be analyzed using an Accupyc 1340 with ASTM foampyc software using nitrogen gas. ASTM Procedure Method C should be used to calculate the percentage open cell. This method simply compares the geometric volume determined using calipers and standard volume calculations to the open cell volume measured by the Accupyc according to the following equation: Percent open cell = open cell volume of sample / geometric volume of sample * 100
[0147] It is recommended that these measurements be performed by Micromeretics Analytical Services, Inc., One Micromeritics Dr, Suite 200, Norcross, GA 30093. More information on this technique is available on the Micromeretics Analytical Services website (www.particletesting.com or www.micromeritics.com) or published in "Analytical Methods in Fine Particle Technology" by Clyde Orr and Paul Webb.
[0148] Test 4: Final Moisture Content of Sheet Articles The final moisture content of the solid sheet article of the present invention is obtained by using a Mettler Toledo HX204 Moisture Analyzer (S / N B706673091). A minimum of 1 g of the dry sheet article is placed on the measurement tray. A standard program is then run with additional program settings of 10 minutes analysis time and 110°C temperature.
[0149] Test 5: Thickness of Sheet Article The thickness of the flexible porous solid sheet articles of the present invention is obtained using a micrometer or feeler gauge, such as a Mitutoyo Corporation Digital Disk Stand Micrometer Model Number IDS-1012E (Mitutoyo Corporation, 965 Corporate Blvd, Aurora, IL, USA 60504), which has a platen with a diameter of 1 inch, weighs about 32 grams, and has a pressure of about 0.09 psi (6.32 gm / cm 2 ) the thickness is measured at an applied pressure of 1000 psi.
[0150] The thickness of a flexible porous dissolvable solid sheet article is measured by raising the platen, placing a portion of the sheet article on a stand directly beneath the platen, carefully lowering the platen to touch the sheet article, releasing the platen, and measuring the thickness of the sheet article in millimeters on a numeric display. Except for uneven, stiffer substrates, the sheet article should be fully extended over all edges of the platen to ensure that the thickness is measured at the least possible surface pressure.
[0151] Test 6: Basis Weight of Sheet Articles The basis weight of the flexible porous dissolvable solid sheet article of the present invention is determined by the weight of the sheet article per area (grams / m 2 The area is calculated as the projected area on a flat surface perpendicular to the outer edges of the sheet article. The solid sheet article of the present invention is cut into 10 cm x 10 cm square samples so that its area is known. Each such square sample is then weighed and the resulting weight is then multiplied by 100 cm. 2 Divide by the known area to determine the corresponding basis weight.
[0152] For irregularly shaped articles, if it is a flat object, the area is calculated based on the area enclosed within the perimeter of such object. Thus, for a spherical object, the area is calculated based on the average diameter, 3.14 x (diameter / 2) 2 The area is calculated as: diameter x length. Thus, for cylindrical objects, the area is calculated based on the average diameter and average length. For irregularly shaped three-dimensional objects, the area is calculated based on the side with the largest outer dimension projected onto a flat surface oriented perpendicular to this side. This can be accomplished by carefully tracing the outer dimensions of the object with a pencil on a piece of graph paper and then calculating the area by approximately counting the squares and multiplying by the known area of the squares, or by taking a photograph of the traced area (shaded for contrast) including a scale and using image analysis techniques.
[0153] Test 7: Density of Wet Premix and Sheet Articles The density of the wet premix is determined by the following equation: Calculated density = weight of wet premix per liter (g / mL).
[0154] The density of the flexible porous solid sheet articles of the present invention is determined by the following equation: Calculated density = basis weight of porous solid / (thickness of porous solid x 1,000). The basis weight and thickness of the flexible porous solid are determined according to the methods described herein.
[0155] Test 8: Specific surface area of sheet article The specific surface area of flexible porous soluble solid sheet articles is measured via a gas adsorption technique. Surface area is a measurement of the exposed surface of a solid sample on a molecular scale. BET (Brunauer, Emmet, and Teller) theory is the most well-known model used to determine surface area and is based on gas adsorption isotherms. Gas adsorption uses physical adsorption and capillary condensation to measure gas adsorption isotherms. This technique is summarized by the following steps: The sample is placed in a sample tube and heated under vacuum or gas flow to remove contaminants on the surface of the sample. The sample weight is obtained by subtracting the empty sample tube weight from the combined weight of the degassed sample and sample tube. The sample tube is then placed on the analysis port and the analysis begins. The first step in this analysis process is to evacuate the sample tube and then measure the free space volume in the sample tube using helium gas at liquid nitrogen temperature. The sample is then evacuated again and the helium gas is removed. The instrument then begins to collect the adsorption isotherm by dosing krypton gas at user-specified intervals until the required pressure measurement is achieved. The samples may then be analyzed using an ASAP2420 with krypton gas adsorption. It is recommended that these measurements be performed by Micromeretics Analytical Services, Inc., One Micromeritics Dr, Suite 200, Norcross, GA 30093. More information on this technique is available on the Micromeretics Analytical Services website (www.particletesting.com or www.micromeritics.com) or published in the book "Analytical Methods in Fine particle Technology" by Clyde Orr and Paul Webb.
[0156] Test 9: Dissolution rate First, the solid sheet is stored for 24 hours at an ambient relative humidity of 50±2% and an ambient temperature of 23±1° C. (i.e., the conditioning step). Following the above initial conditioning step, a 25 mm hollow hole punch is used to cut disks of 25 mm diameter from the first large solid sheet. The required number of foam disks is set such that the total mass of all foam disks is 0.1 g or more.
[0157] The required number of foam discs are then stacked in a top-to-bottom orientation and placed inside an Omnifit™ EZ chromatography column (006EZ-25-10-AF) with an internal diameter of 25 mm, a length of 100 m, and an adjustable and removable end piece. The stack of foam discs is placed inside the column such that the direction of flow through the column is perpendicular to the top surface of the foam discs. Once placed inside the column, the end piece is inserted into the column and adjusted until the vertical distance between the two internal frits is equal to the thickness of the stack of foam discs.
[0158] Masterflex silicone tubing (MFLEX SILICONE #25 25') and Masterflex peristaltic pump (MFLX L / S 1CH 300R 115 / 230 13124) are used to control the flow of water through the column. The system flow rate is calibrated by running water through the pump, tubing, and empty column at different pump RPM settings and recording the volume of water collected over a specified time period. A flow rate of 5 liters / hour was used for all experiments.
[0159] Both the inlet and outlet tubes are placed in a 1 liter beaker containing 500 mL of deionized water at ambient temperature. The beaker is placed on a magnetic stirrer plate and a magnetic stir bar with a length of 23 mm and a thickness of 10 mm is placed in the beaker and the stirrer rotation speed is set to 300 rpm. A Mettler Toledo S230 conductivity meter is calibrated to 1413 μS / cm and the probe is placed in the beaker of water.
[0160] Begin the water flow through the system. When the first drop of water is visually seen contacting the foam in the column, begin the data recording function on the conductivity meter. Record data for at least 20 minutes.
[0161] To estimate the time required for the foam to reach 90 or 95% dissolution, a calibration curve is first made in which layers of foam disks are dropped one by one into a stirred beaker of 500 mL deionized water. The mass of each individual foam disk is recorded along with the conductivity after 5 minutes. This process is repeated for up to a total of 5 disks. A linear function is fitted to the data and then used to estimate the maximum conductivity for each dissolution test based on the total mass of foam disks placed in the column. The dissolution rate is then calculated as follows: % dissolved = experimentally measured conductivity / maximum conductivity * 100
[0162] The time required to achieve 90 or 95% dissolution is then obtained from this calculated data. The calibration procedure is repeated for each test formula.
[0163] Test 10: Elasticity of solid sheets The extension of the solid sheet is determined as a measure of the elasticity of the solid sheet by using a Material Testing System instrument (MTS Tensile Tester Criterion® Series, Model 42). The solid sheet is preconditioned and equilibrated at 10% relative humidity and 23 + / - 1°C for 24 hours. After preconditioning, test samples (e.g., strips) are cut with a width of 20 mm and a length of 100 mm. The test strip is firmly clamped on both sides to the mounting platform of the instrument (to the extent that it prevents slippage during testing) and a load is applied at a constant head speed of 200 mm per minute to stretch the strip at the midpoint at a rate of 100 mm per minute. The breaking strain (mm) is recorded as the total distance the strip extends (i.e., the extension) when it breaks.
[0164] Test 11: Flexibility of solid sheets The flexibility of a solid sheet is measured as follows. A number of semi-automatic washing machines (e.g., Haier XPB60-187BS FM) are used. The semi-automatic washing machines include two sections: a tub for washing and rinsing, and a spin-dry machine for spin-drying. Each machine is operated according to the following steps: (1) dissolving the recommended amount of powder detergent (described further below) in an appropriate amount of water (e.g., 32 g of powder in 13 L of water for 2 minutes), (2) manually adding the fabrics to the water in the tub, (3) allowing the fabrics to soak for a period of time (e.g., 3 minutes) without agitation, (4) standard automatic machine wash (e.g., 20 minutes), (5) two consecutive rinses (e.g., 1 minute spin-dry in the spin-dry machine and 3 minutes of wash agitation in the tub with 23 L of water), and (6) a final rinse with the addition of the test sample. Step (6) specifically involves adding 13 L of water to the tub, followed by the addition of the test sample to the water, followed by 2 minutes of automatic machine agitation to ensure complete dissolution of the sample. The previously dehydrated fabrics are then placed back into the bath solution and subjected to one minute of automatic mechanical agitation. The fabrics are then dehydrated for 30 seconds and allowed to sit in the dehydrator for 10 minutes before being removed.
[0165] The water used had a hardness of 74 ppm and 61 ppm CaCl 2 and 13 ppm MgCl 2 and at a temperature of 28°C for all soaking, washing and rinsing steps. The total fabric input weight is 1.2 kg (including 4 terry cloth hand towels as test fabrics, the remaining items contain only cotton fabrics and poly-cotton blend in a 6:4 ratio). The detergent used is ARIEL powder detergent (The Procter & Gamble Company) obtained from the Philippines. 32 g of detergent is added to the wash water. The terry cloth test fabrics are line dried for 36-48 hours in a controlled room at 32°C / 80% relative humidity.
[0166] To quantify softness, the coefficient of friction of each terry fabric is measured. The kinetic coefficient of friction is measured using a Thwing Albert Friction / Peel Tester FP-2250 by attaching a swatch cut from the terry fabric to a sled and dragging the sled at a fixed speed across a portion of the remaining terry fabric. A lower measured coefficient of friction indicates improved softness.
[0167] Test 12: Anti-wrinkle effect of solid sheets The anti-wrinkle effect of a solid sheet is measured as follows. A number of semi-automatic washing machines (e.g., Haier XPB60-187BS FM) are used. The semi-automatic washing machines include two sections: a tub for washing and rinsing, and a spin-dry machine for spin-drying. Each machine is operated according to the following steps: (1) dissolving the recommended amount of powder detergent (described further below) in an appropriate amount of water (e.g., 32 g of powder in 13 L of water for 2 minutes), (2) manually adding the fabrics to the water in the tub, (3) allowing the fabrics to soak for a period of time (e.g., 3 minutes) without agitation, (4) standard automatic machine wash (e.g., 20 minutes), (5) two consecutive rinses (e.g., 1 minute spin-dry in the spin-dry machine and 3 minutes of wash agitation in the tub with 23 L of water), and (6) a final rinse with the addition of the test sample. Step (6) specifically involves adding 13 L of water to the tub, followed by the addition of the test sample to the water, followed by 2 minutes of automatic machine agitation to ensure complete dissolution of the sample. The previously dehydrated fabrics are then placed back into the bath solution and subjected to one minute of automatic mechanical agitation. The fabrics are then dehydrated for 30 seconds and allowed to sit in the dehydrator for 10 minutes before being removed.
[0168] The water used had a hardness of 74 ppm and 61 ppm CaCl 2 and 13 ppm MgCl 2and at a temperature of 28°C for all soaking, washing and rinsing steps. The total fabric input weight is 1.2 kg (including 4 test polyester fabrics, 4 test poly-cotton fabrics, 4 test cotton knit fabrics and 4 test cotton woven fabrics, the remaining items containing only cotton fabrics and poly-cotton blend in a 6:4 ratio). The detergent used is ARIEL powder detergent (The Procter & Gamble Company) obtained from the Philippines. 32 g of detergent is added to the wash water. The terry cloth test fabrics are line dried for 36-48 hours in a controlled room at 32°C / 80% relative humidity.
[0169] To assess wrinkles, the washed and line-dried fabrics are visually evaluated by a panel of trained operators. In each panel test, the panelists are presented with a total of 16 polyester fabrics consisting of four sets of four fabrics, each set corresponding to the fabric softener with which the fabrics in that set were washed, or, for one control set, 40 mL of Downy Fabric Conditioner (The Procter & Gamble Company) from the Philippines is always used. The washed and line-dried test fabrics are independently ranked by individual panelists, each of whom assigns a grade score of 4 to the set of fabrics with the most visible wrinkles and a grade score of 1 to the set of fabrics with the least wrinkles. Each panel includes 6-8 people. The grade scores assigned to each softener are averaged and the standard deviation is calculated to determine the variation between panelists. The exact same evaluation method is applied to other types of test fabrics. EXAMPLES
[0170] Example 1: Improved Stability of Aerated Premixes with Preferred Range of Plasticizer to Cationic Surfactant Ratios Solid sheets having the formulations (Formulation A and Comparative Formulations a and b) shown in Table 1 (Wet Premix) and Table 2 (Dry Sheets) below are prepared according to the rotary drum heating / drying configuration in section "III. Process for Making Solid Sheets."
[0171] [Table 1] a Polyvinyl alcohol with a degree of hydrolysis of 88% and a degree of polymerization of approximately 1700 available from Sigma Aldrich. b Rewoquat DEEDMAC available from Evonik Industries.
[0172] [Table 2] a Polyvinyl alcohol with a degree of hydrolysis of 88% and a degree of polymerization of approximately 1700 available from Sigma Aldrich. b Rewoquat DEEDMAC available from Evonik Industries.
[0173] Specifically, a wet premix (i.e., a slurry) containing the solid sheet ingredients and additional water is first prepared to obtain a total solids content of about 35% by weight (i.e., the total water content in the slurry is about 65% by weight). The slurry preparation method is as follows: 1. First, add the water and glycerin together into a glass beaker and stir at 200 rpm using an overhead stirrer. 2. With continued stirring, the polyvinyl alcohol is then slowly added to the beaker containing the water and glycerin, without causing the solution to foam or the polyvinyl alcohol to clump. 3. The beaker is then placed in a water bath and heated with continued stirring to 80° C. The beaker is covered with cling film or tin foil to reduce water evaporation and mixing is allowed to continue for at least 1.0 hour. 4. The remaining ingredients are weighed and added together in a separate glass beaker. The remainder of the water needed to achieve a total water content of 65% in the slurry is also added to this beaker. 5. Place the beaker in an 80°C water bath and stir its contents using an overhead stirrer at 500 rpm for at least 30 minutes. 6. Once the predefined mixing time has been reached in both beakers, add both contents together into a single glass beaker followed by continuous stirring at 500 rpm and maintaining the temperature at 80° C. for at least an additional 30 minutes.
[0174] The premix is then aerated by using an Aeros A20 continuous aerator. After aeration, the aerated premix is collected and then dried in a rotary drum dryer to produce a solid sheet. The settings and conditions for aeration and drum drying are shown in Table 3 below.
[0175] [Table 3]
[0176] Further, to compare the aeration stability of the premix for the different formulations, 60 mL of the aerated premix is placed in a beaker, the beaker is kept in a water bath, the water temperature is set to 60° C., and the wet premix is continuously stirred at 50 RPM for 30 minutes using a laboratory overhead mixer. The initial density and density at 30 minutes of the aerated premix are measured according to “Test 7: Density of Wet Premix and Sheet Article” and are shown in Table 4 below. The ratio of the density at 0 minutes to the density at 30 minutes is used as a measurement of the stability of the aerated premix. Furthermore, the density of the solid sheet obtained by the different formulations is also determined. The data in Table 4 show that the ratio of the density of the premix at 30 minutes to the density of the premix at 0 minutes of the comparative formulations a or b, which have too high or too low ratios of glycerin to DEEDMAC (i.e., 2.00 or 3.07, respectively), is very high, while the ratio of the formulation A is only 1.27. In particular, the increase in density of formulation A at 30 minutes storage is very limited (e.g., from 0.310 g / mL to 0.395 g / mL) and the density remains low (e.g., 0.395 g / mL) compared to the sharp increase in density of the premix after aeration of comparative formulations a and b (rising to over 0.800 g / mL). Furthermore, as also shown in Table 4, the solid sheet of formulation A has a significantly lower density compared to comparative formulation a (0.204 g / mL vs. 0.455 g / mL), and for comparative formulation b, no sheet is obtained because the premix is too unstable. Thus, when the ratio of plasticizer (e.g., glycerin) to cationic surfactant (e.g., DEEDMAC) is within the preferred range (e.g., 0.9-2), the stability of the aerated premix is significantly improved.
[0177] [Table 4]
[0178] Example 2: Effect of starch concentration on elasticity of solid sheets Solid sheets having the formulations (Formulations A-C) shown in Table 5 (wet premix) and Table 6 (dry sheet) below are prepared according to the rotary drum heating / drying configuration in section "III. Process for making solid sheets" as in Example 1.
[0179] [Table 5] a Polyvinyl alcohol with a degree of hydrolysis of 88% and a degree of polymerization of approximately 1700 available from Sigma Aldrich. b Rewoquat DEEDMAC available from Evonik Industries.
[0180] [Table 6] a Polyvinyl alcohol with a degree of hydrolysis of 88% and a degree of polymerization of approximately 1700 available from Sigma Aldrich. b Rewoquat DEEDMAC available from Evonik Industries.
[0181] The elongation of the solid sheets with formulations A-C was measured according to "Test 10: Elasticity of Solid Sheets" to characterize the elasticity of solid sheets and is shown in Table 7 below. The data shows that the elongation of the solid sheet with 3.4% starch (formulation A) is reduced to a much lesser extent (i.e., 21%) compared to the significant reduction in elongation of the solid sheet with formulation C containing 5% starch (i.e., 35%). Thus, too much starch may impair the elasticity of the sheet article. Therefore, it is further preferred that the solid sheet article contains no more than 5% starch by weight of the solid sheet article.
[0182] [Table 7]
[0183] Example 3: OCF Structures in Solid Sheets Made by Various Heating / Drying Configurations Solid sheets having the formulations (Formulations 1 and 2) shown in Table 8 (wet premix) and Table 9 (dry sheets) below are prepared according to various heating / drying configurations in section "III. Process for making solid sheets."
[0184] [Table 8]
[0185] [Table 9]
[0186] The viscosity of the wet premix composition of Formulation 1 is about 14309.8 cp. After aeration, the average density of such aerated wet premix is about 0.25 g / cm. 3 The viscosity of the wet premix composition of Formulation 2 is about 19254.6 cp. After aeration, the average density of such aerated wet premix is about 0.225 g / cm. 3 It is.
[0187] Flexible porous dissolvable solid sheets 1 and 2 are prepared from the above wet premixes described in Table 8 using a continuous aerator (Aeros) and a rotary drum dryer using the settings and conditions described in Example 1 above (see Table 3).
[0188] Flexible Porous Dissolvable Solid Sheet 3 is also prepared from the above wet premix described in Table 8 using a continuous aerator (Oakes) and a mold placed on a hot plate (providing bottom conduction heating) using the following settings and conditions set out in Table 10 below.
[0189] [Table 10]
[0190] Additionally, flexible porous dissolvable solid sheets 4 and 5 are prepared from the above wet premixes described in Table 8 using a continuous aerator (Oakes) and a mold placed on an impingement oven using the following settings and conditions set forth in Table 11 below.
[0191] [Table 11]
[0192] Tables 12-15 below summarize various physical parameters and pore structures measured for Sheets 1-5 made from the wet premix and drying process described above.
[0193] [Table 12]
[0194] [Table 13]
[0195] [Table 14]
[0196] [Table 15]
[0197] The above data demonstrates that when the heating direction is offset from the gravity direction throughout most of the drying process, the resulting solid sheets (e.g., sheets 1, 2, and 3) can have a top surface with larger pore openings and reduced pore size variation in different regions along the thickness direction of such sheet articles, compared to solid sheet articles (e.g., sheets 4 and 5) obtained when the heating direction is substantially aligned with the gravity direction. In particular, the above table shows that sheets 1, 2, and 3 have top surface average pore sizes greater than 100 μm, whereas sheets 4 and 5 do not.
[0198] Example 4: Exemplary Solid Sheet Articles The following are examples of solid sheet articles. Sheets I-V having the formulations shown in Table 16 below are prepared similarly to Example 1. Furthermore, each sheet can be stacked to form a multi-layer sheet article having 2-20 layers each.
[0199] [Table 16]
[0200] Additionally, solid sheet articles containing a coating composition (i.e., juice) can be prepared by applying one or more of juices i-v shown below in Table 17 between the sheets (e.g., one or more of sheets I-V) during lamination of the sheets. An exemplary solid sheet article containing a coating composition can be prepared by applying juice i between sheets I.
[0201] [Table 17]
[0202] Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0203] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.
[0204] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention. This specification discloses the following inventions. 1. A flexible porous dissolvable solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant, the solid sheet article is characterized by (i) a percent open cell content of between 80% and 100%, and (ii) an overall average pore size of between 100 μm and 2000 μm; A flexible porous dissolvable solid sheet article, wherein the weight ratio of said plasticizer to said cationic surfactant is 0.9-2. 2. 2. The flexible porous dissolvable solid sheet article according to 1, wherein the weight ratio of the plasticizer to the cationic surfactant is from 1 to 1.8, preferably from 1.1 to 1.7, and more preferably from 1.2 to 1.6. 3. 3. The flexible porous dissolvable solid sheet article according to 1 or 2, wherein the solid sheet article comprises 1% to 65%, preferably 10% to 60%, more preferably 15% to 55%, even more preferably 20% to 50%, and most preferably 22% to 40% of the plasticizer by weight of the total weight of the solid sheet article, and / or the solid sheet article comprises 1% to 50%, preferably 5% to 45%, more preferably 10% to 40%, and most preferably 15% to 35% of the fabric softener by weight of the total weight of the solid sheet article. 4. the plasticizer is selected from the group consisting of polyols, copolyols, polycarboxylic acids, polyesters, and dimethicone copolyols; Preferably, the plasticizer is selected from the group consisting of glycerin, ethylene glycol, polyethylene glycol, propylene glycol, and combinations thereof; More preferably, the plasticizer is glycerin. 5. the cationic surfactant is a quaternary ammonium compound and / or an amine compound; Preferably, the cationic surfactant is selected from the group consisting of diester quaternary ammonium (DEQA) compounds, mono-long chain alkyl quaternary ammonium compounds, di-long chain alkyl quaternary ammonium compounds, mono-long chain alkyl amine compounds, and any combination thereof; Even more preferably, the cationic surfactant is selected from the group consisting of alkyltrimethylammonium compounds or amine precursors thereof, dialkyldimethylammonium compounds or amine precursors thereof, methyldiethanolamine-based (MDEA-based) quaternary ammonium compounds or amine precursors thereof, methyldiisopropanolamine-based (MDIPA-based) quaternary ammonium compounds or amine precursors thereof, triethanolamine-based (TEA-based) quaternary ammonium compounds or amine precursors thereof, and any combination thereof; 5. The flexible porous dissolvable solid sheet article according to any one of 1 to 4, most preferably, the cationic surfactant is selected from the group consisting of behenyl trimethyl ammonium chloride; stearyl trimethyl ammonium chloride; cetyl trimethyl ammonium chloride; lauryl trimethyl ammonium chloride; hydrogenated tallow alkyl trimethyl ammonium chloride, dimethyl hydroxyethyl lauryl ammonium chloride, dialkyl (14-18) dimethyl ammonium chloride, ditallow alkyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dicetyl dimethyl ammonium chloride, N,N-di(acyloxyethyl)-N,N-dimethyl ammonium chloride, N,N-di(acyloxyisopropyl)-N,N-dimethyl ammonium methyl sulfate, N,N-di(acyloxyethyl)-N,N-methyl hydroxyethyl ammonium methyl sulfate, and any combination thereof. 6. 6. The flexible porous dissolvable solid sheet article according to any one of 1 to 5, wherein the solid sheet article comprises 1% to 60%, preferably 5% to 50%, more preferably 10% to 45%, even more preferably 15% to 40%, and most preferably 20% to 30% of the water-soluble polymer by weight of the total weight of the solid sheet article. 7. the water soluble polymer is selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, polyalkylene oxide, starch and starch derivatives, pullulan, gelatin, hydroxypropyl methylcellulose, methylcellulose, carboxymethylcellulose, and any combination thereof; 7. The flexible porous dissolvable solid sheet article according to any one of 1 to 6, wherein the water-soluble polymer has a weight average molecular weight of 5,000 to 400,000 daltons, more preferably 10,000 to 300,000 daltons, even more preferably 15,000 to 200,000 daltons, and most preferably 20,000 to 150,000 daltons. 8. The water-soluble polymer comprises polyvinyl alcohol; 8. The flexible porous dissolvable solid sheet article according to claim 7, wherein the solid sheet article comprises from 1% to 60%, preferably from 5% to 50%, more preferably from 10% to 40%, and most preferably from 15% to 40% of the polyvinyl alcohol by total weight of the solid sheet article. 9. The water-soluble polymers include polyvinyl alcohol and starch; 8. The flexible porous dissolvable solid sheet article according to 7, wherein the solid sheet article comprises from 1% to 60%, preferably from 5% to 50%, more preferably from 10% to 40%, and most preferably from 15% to 35% of the polyvinyl alcohol and from 0.001% to 5%, preferably from 0.01% to 4.5%, more preferably from 0.1% to 4% of the starch by total weight of the solid sheet article. 10. The water-soluble polymer comprises a first polyvinyl alcohol having a first weight average molecular weight and a second polyvinyl alcohol having a second weight average molecular weight, the first weight average molecular weight is preferably 5,000 to 50,000 daltons, more preferably 10,000 to 40,000 daltons, even more preferably 15,000 to 35,000 daltons, and most preferably 20,000 to 30,000 daltons, and the second weight average molecular weight is preferably 20,000 to 400,000 daltons, more preferably 30,000 to 300,000 daltons, even more preferably 40,000 to 200,000 daltons, and most preferably 50,000 to 150,000 daltons; 8. The flexible porous dissolvable solid sheet article according to 7, wherein the solid sheet article preferably comprises 1% to 60%, preferably 2% to 30%, more preferably 3% to 20%, and most preferably 4% to 15% of the first polyvinyl alcohol and 2% to 60%, preferably 4% to 40%, more preferably 6% to 30%, and most preferably 8% to 25% of the second polyvinyl alcohol by total weight of the solid sheet article. 11. 11. The flexible porous dissolvable solid sheet article according to any one of 1 to 10, wherein the solid sheet article comprises 0.01% to 20%, preferably 0.1% to 12%, more preferably 0.5% to 8%, and most preferably 1% to 5% of a nonionic surfactant by weight of the total weight of the solid sheet article. 12. 12. The flexible porous dissolvable solid sheet article of any one of 1 to 11, wherein the solid sheet article comprises two or more flexible porous dissolvable sheets, and the coating composition is present on at least one surface of at least one of the two or more sheets, provided that the coating composition is not present on an outer surface of any of the solid sheet articles, and preferably the coating composition comprises one or more components selected from the group consisting of additional surfactants, fragrances, silicones, emulsifiers, solvents, rheology modifiers, enzymes, bleaching agents, colorants, gloss agents, dye transfer inhibitors, deposition aids, antimicrobial agents, non-film forming polymers, antifoam agents, defoamers, and combinations thereof. 13. The additional surfactant is 6 ~C 20 Linear alkylbenzene sulfonates (LAS), C with weight average degree of alkoxylation ranging from 0.5 to 10 6 ~C 20 Linear or branched chain alkyl alkoxy sulfates (AAS), C having a weight average degree of alkoxylation ranging from 5 to 15 6 ~C 20 Linear or branched alkyl alkoxylated alcohols (AA), C 6 ~C 20 and / or selected from the group consisting of linear or branched chain alkyl sulfates (AS), alkyl sulfates, alkyl ether sulfates, alkyl amphoacetates, and any combination thereof; The perfume is selected from the group consisting of free perfume, perfume microcapsules, and any combination thereof; and / or and / or the silicone is selected from the group consisting of vinyl dimethicone / methicone silsesquioxane crosspolymer, polysilicone, polymethylsilsesquioxane, diphenyl dimethicone / vinyl diphenyl dimethicone / silsesquioxane crosspolymer, and any combination thereof; the emulsifier is selected from the group consisting of mono- and diglycerides, fatty alcohols, polyglycerol esters, propylene glycol esters, sorbitan esters, polyhydroxystearic acid, and any combination thereof; and / or the solvent is selected from the group consisting of glycerol, propylene glycol, 1,3-propanediol, diethylene glycol, dipropylene glycol, ethanolamine, ethanol, water, and any combination thereof; and / or the rheology modifier is selected from the group consisting of cellulose and derivatives; guar and guar derivatives; polyethylene oxide, polypropylene oxide, and POE-PPO copolymers; polyvinylpyrrolidone, crosslinked polyvinylpyrrolidone and derivatives; polyvinyl alcohol and derivatives; polyethyleneimine and derivatives; inorganic particles such as sodium carbonate and sodium sulfate; silicon dioxide; water-swellable clays; gums; and any combination thereof; and / or 13. The flexible porous dissolvable solid sheet article of claim 12, wherein the deposition aid is selected from the group consisting of cationic polymers, amphoteric polymers, and any combination thereof, and the cationic polymer is preferably selected from cationic hydroxyethyl cellulose. 14. 14. The flexible porous dissolvable solid sheet article according to claim 12 or 13, wherein a weight ratio of the coating composition to the two or more sheets is from 0.01 to 2, preferably from 0.02 to 1, more preferably from 0.05 to 0.8, and most preferably from 0.08 to 0.5. 15. The solid sheet article comprises: an open cell content of 85% to 100%, preferably 90% to 100%, and / or an overall average pore size of 150 μm to 1000 μm, preferably 200 μm to 600 μm, and / or an average cell wall thickness of 5 μm to 200 μm, preferably 10 μm to 100 μm, more preferably 10 μm to 80 μm, and / or a final moisture content of 0.5% to 25% by weight of said solid sheet article, preferably 1% to 20% by weight, more preferably 3% to 15% by weight, and / or a thickness of each sheet between 0.5 mm and 4 mm, preferably between 0.7 mm and 3 mm, more preferably between 0.8 mm and 2 mm, and most preferably between 1 mm and 1.5 mm; and / or 50g / m 2 ~250g / m 2 , preferably 80 g / m 2 ~230g / m 2 , more preferably 100 g / m 2 ~220g / m 2 and / or 0.05g / cm 3 ~0.5g / cm 3 , preferably 0.06 g / cm 3 ~0.4g / cm 3 , more preferably 0.07 g / cm 3 ~0.3g / cm 3 , most preferably 0.08 g / cm 3 ~0.25g / cm 3 and / or ·0.03m 2 / g~0.25m 2 / g, preferably 0.04m 2 / g~0.22m 2 / g, more preferably 0.05m 2 / g~0.2m 2 / g, most preferably 0.1m 2 / g~0.18m 2 15. The flexible porous dissolvable solid sheet article according to any one of 1 to 14, characterized by a specific surface area of 1 / g. 16. 1. A process for making a solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant, the weight ratio of said plasticizer to said cationic surfactant being between 0.9 and 2, said process comprising: a) preparing a wet premix comprising the water-soluble polymer, the plasticizer, and the cationic surfactant; b) aerating the wet premix to form an aerated wet premix; c) forming the aerated wet premix into a sheet having opposed first and second surfaces; d) drying said formed sheet to produce said solid sheet article. 17. 17. The process of making a solid sheet article according to claim 16, wherein step d) is carried out along a heating direction forming a decreasing temperature gradient from the first side to the second side of the formed sheet at a temperature of 70°C to 200°C, preferably 90°C to 140°C, for a time period of 5 minutes to 300 minutes, preferably 10 minutes to 120 minutes, said heating direction being substantially opposite to the direction of gravity for more than half of the drying time, preferably for more than 75% of the drying time. 18. The wet premix is heated at 40° C. for 1 s -1 and / or the aerated wet premix has a density of 0.05 to 0.7 g / mL, preferably 0.15 g / mL to 0.6 g / mL, more preferably 0.2 g / mL to 0.5 g / mL, and most preferably 0.25 g / mL to 0.45 g / mL.
Claims
1. A flexible porous dissolvable solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant, the solid sheet article is characterized by (i) a percent open cell content of from 80% to 100%, and (ii) an overall average pore size of from 100 μm to 2000 μm; the water-soluble polymer comprises polyvinyl alcohol; the plasticizer is selected from the group consisting of glycerin, ethylene glycol, polyethylene glycol, propylene glycol, and mixtures thereof; the cationic surfactant is a quaternary ammonium compound and / or an amine compound; A flexible porous dissolvable solid sheet article, wherein the weight ratio of said plasticizer to said cationic surfactant is from 1.2 to 1.
6.
2. 2. The flexible porous dissolvable solid sheet article of claim 1, wherein said solid sheet article comprises from 1% to 65% of said plasticizer by total weight of said solid sheet article, and / or said solid sheet article comprises from 1% to 50% of said cationic surfactant by total weight of said solid sheet article.
3. 3. The flexible porous dissolvable solid sheet article of claim 1 or 2, wherein said plasticizer is glycerin.
4. The flexible porous dissolvable solid sheet article of any one of claims 1 to 3, wherein said cationic surfactant is a diester quaternary ammonium (DEQA) compound.
5. The flexible porous dissolvable solid sheet article of any one of claims 1 to 4, wherein said solid sheet article comprises from 1% to 60% of said water soluble polymer by total weight of said solid sheet article.
6. 10. The flexible porous dissolvable solid sheet article of claim 1, wherein said water soluble polymer comprises polyvinyl alcohol and starch.
7. 2. The flexible porous dissolvable solid sheet article of claim 1, wherein said water soluble polymer comprises a first polyvinyl alcohol having a first weight average molecular weight and a second polyvinyl alcohol having a second weight average molecular weight, said first weight average molecular weight being from 5,000 to 50,000 Daltons and said second weight average molecular weight being from 20,000 to 400,000 Daltons.
8. 8. The flexible porous dissolvable solid sheet article of any one of claims 1 to 7, wherein said solid sheet article comprises from 0.01% to 20% of a non-ionic surfactant by total weight of said solid sheet article.
9. 9. The flexible porous dissolvable solid sheet article of any one of claims 1 to 8, wherein the solid sheet article comprises two or more flexible porous dissolvable sheets, and the coating composition is present on at least one surface of at least one of the two or more sheets, with the proviso that the coating composition is not present on an exterior surface of any of the solid sheet articles.
10. 10. The flexible porous dissolvable solid sheet article of claim 9, wherein the coating composition comprises one or more components selected from the group consisting of additional surfactants, fragrances, silicones, emulsifiers, solvents, rheology modifiers, enzymes, bleaching agents, colorants, brighteners, dye transfer inhibitors, deposition aids, antimicrobial agents, non-film forming polymers, antifoam agents, defoamers, and combinations thereof.
11. The additional surfactant is 6 ~C 20 Linear alkylbenzene sulfonates (LAS), C having a weight average degree of alkoxylation ranging from 0.5 to 10 6 ~C 20 Linear or branched chain alkyl alkoxy sulfates (AAS), C having a weight average degree of alkoxylation ranging from 5 to 15 6 ~C 20 Linear or branched alkyl alkoxylated alcohols (AA), C 6 ~C 20 and / or selected from the group consisting of linear or branched alkyl sulfates (AS), alkyl sulfates, alkyl ether sulfates, alkyl amphoacetates, and any combination thereof; The perfume is selected from the group consisting of free perfume, perfume microcapsules, and any combination thereof; and / or and / or the silicone is selected from the group consisting of vinyl dimethicone / methicone silsesquioxane crosspolymer, polysilicone, polymethylsilsesquioxane, diphenyl dimethicone / vinyl diphenyl dimethicone / silsesquioxane crosspolymer, and any combination thereof; and / or the emulsifier is selected from the group consisting of mono- and diglycerides, fatty alcohols, polyglycerol esters, propylene glycol esters, sorbitan esters, polyhydroxystearic acid, and any combination thereof; the solvent is selected from the group consisting of glycerol, propylene glycol, 1,3-propanediol, diethylene glycol, dipropylene glycol, ethanolamine, ethanol, water, and any combination thereof; and / or and / or the rheology modifier is selected from the group consisting of cellulose and derivatives; guar and guar derivatives; polyethylene oxide, polypropylene oxide, and POE-PPO copolymers; polyvinylpyrrolidone, crosslinked polyvinylpyrrolidone and derivatives; polyvinyl alcohol and derivatives; polyethyleneimine and derivatives; inorganic particles; silicon dioxide; water-swellable clays; gums; and any combination thereof; 11. The flexible porous dissolvable solid sheet article of claim 10, wherein said deposition aid is selected from the group consisting of cationic polymers, amphoteric polymers, and any combination thereof.
12. The flexible porous dissolvable solid sheet article of any one of claims 9 to 11, wherein the weight ratio of said coating composition to said two or more sheets is from 0.01 to 2.
13. The solid sheet article comprises: Percent open cell content between 85% and 100%, and / or an overall average pore size between 150 μm and 1000 μm, and / or an average cell wall thickness of 5 μm to 200 μm, and / or a final moisture content of from 0.5% to 25% by weight of said solid sheet article, and / or a thickness of each sheet between 0.5 mm and 4 mm, and / or 50 grams / m 2 ~250g / m 2 and / or 0.05 grams / cm 3 ~0.5 grams / cm 3 and / or ・0.03m 2 / g to 0.25m 2 The flexible porous dissolvable solid sheet article of any one of claims 1 to 12, characterized by a specific surface area of 1 / g.
14. 1. A process for making a solid sheet article comprising a water soluble polymer, a plasticizer, and a cationic surfactant, the weight ratio of said plasticizer to said cationic surfactant being from 1.2 to 1.6, said process comprising: a) preparing a wet premix comprising the water-soluble polymer, the plasticizer, and the cationic surfactant; b) aerating the wet premix to form an aerated wet premix; c) forming the aerated wet premix into a sheet having opposed first and second surfaces; d) drying the formed sheet to produce the solid sheet article, wherein the water soluble polymer comprises polyvinyl alcohol; the plasticizer is selected from the group consisting of glycerin, ethylene glycol, polyethylene glycol, propylene glycol, and mixtures thereof; A process for making a solid sheet article, wherein said cationic surfactant is a quaternary ammonium compound and / or an amine compound.
15. 15. The process of making a solid sheet article of claim 14, wherein step d) is carried out along a heating direction forming a decreasing temperature gradient from the first side to the second side of the formed sheet at a temperature of 70°C to 200°C for a time period of 5 minutes to 300 minutes, the heating direction being substantially opposite to a direction of gravity for more than half of the drying time.
16. The wet premix was heated at 40° C. for 1 s -1 15. The process for making the solid sheet article of claim 14, wherein the solid sheet article has a viscosity of from 1,000 cp to 25,000 cp as measured by .
17. The process for making a solid sheet article of claim 14, wherein the aerated wet premix has a density of 0.05 to 0.7 g / mL.
Citation Information
Patent Citations
Non-foaming personal care composition in article form
JP2011516614A
A continuous process for producing articles that dissolve upon use to deliver surfactants.
JP2014510190A
Dissolvable solid hair dye articles
JP2014515404A
Process of making article for dissolution upon use to deliver surfactants
JP2015083591A
Personal care compositions in the form of soluble articles
JP2015536920A